Propylene polymer production method

By using biomass-derived reaction inhibitors with moisture in specific concentration ranges during the production process of propylene polymers and controlling multi-step reaction conditions, the catalytic activity reduction and blocking caused by impurities in biomass reaction inhibitors is solved. The problem of forming resins is achieved, and stable production and high-quality polymers are achieved.

CN119403853APending Publication Date: 2025-02-07JAPAN POLYPROPYLENE CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380047934.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-24
Filing Date
2023-05-30
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

When producing propylene-based polymers using reaction inhibitors derived from biomass, the presence of impurities leads to a decrease in catalytic activity and the formation of a bulk resin, which affects the stability and quality of production.

Method used

By adding biomass-derived reaction inhibitors containing moisture in a specific concentration range during the production of propylene polymers, and using multiple steps and reactors in the polymerization reactor, the reaction conditions are controlled to inhibit the reduction of catalytic activity by using a plurality of steps and reactors in the polymerization reactor. and the formation of block resin.

Benefits of technology

It is achieved that when using reaction inhibitors derived from biomass, the production stability and quality of propylene-based polymers are maintained, the environmental load is reduced, and the production efficiency is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005194346400000501
    Figure BDA0005194346400000501
  • Figure BDA0005194346400000511
    Figure BDA0005194346400000511
Patent Text Reader

Abstract

Provided is a method for producing a propylene-based polymer in which a first propylene-based polymer is produced in the presence of an olefin polymerization catalyst in a first step, and a second propylene-based polymer is produced in the presence of the first propylene-based polymer in a subsequent second step. A biomass-derived reaction inhibitor containing 5-2000 ppm by mass of water is added during at least one period selected from the group consisting of the first step, the second step, and the first and second steps.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing a propylene polymer. Background Art

[0002] Among thermoplastic resins, propylene-based polymers obtained by homopolymerization of propylene or copolymerization of propylene and comonomers in the presence of an olefin polymerization catalyst are lightweight, excellent in rigidity, heat resistance and chemical resistance, and low-cost. Therefore, propylene-based polymers are widely used in components such as interior materials and bumpers of automobiles and many general household appliances.

[0003] In the production of such propylene-based polymers, multiple polymerization reactors are used, and each polymer with different molecular weights and comonomer contents is polymerized in each polymerization reactor, thereby giving the propylene-based polymer a wide composition distribution and improving the function of the final product. For example, the following method is implemented: after the low molecular weight polymer is polymerized in the polymerization reactor of the front section, the high molecular weight polymer is polymerized in the polymerization reactor of the back section to expand the molecular weight distribution of the polymer, thereby improving its formability. In addition, the following method is implemented: the crystalline propylene homopolymer is polymerized in the polymerization reactor of the front section, and the non-crystalline propylene-ethylene copolymer with a large comonomer content is polymerized in the polymerization reactor of the back section to produce the so-called propylene-based block copolymer, thereby improving the balance between the rigidity and the impact resistance of the propylene-based polymer.

[0004] In such propylene polymers, the content ratio of each polymer produced in each polymerization reactor has a strong influence on the physical properties of the final product. Therefore, it is known to add a reaction inhibitor having the function of deactivating the catalyst for olefin polymerization in the production process of propylene polymers. For example, Patent Documents 1 and 2 disclose the use of active hydrogen compounds (e.g., alcohols) as reaction inhibitors from the viewpoint of not only controlling the content ratio of each propylene polymer, but also suppressing the adhesion of propylene polymers and the quality deterioration of the generation of aggregated block polymers, gels, etc. that are accompanied.

[0005] Meanwhile, in recent years, there have been attempts to reduce environmental load or create a recycling-oriented society by converting raw materials derived from petrochemical products into raw materials derived from biomass. For example, Patent Document 3 proposes a packaging film in which a resin film containing polyester obtained by using ethylene glycol derived from biomass and dicarboxylic acid derived from fossil fuels is used as a substrate layer. Patent Document 4 reports the development of a process for ultimately producing propylene from a biomass raw material and producing bio-polypropylene by using the propylene.

[0006] Furthermore, Non-Patent Document 1 reports on a study on the removal of impurities that may inhibit polymerization activity when carrying out the production of polypropylene from a biomass raw material.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Laid-Open (JP-A) No. S61-69821

[0010] Patent Document 2: JP-A No. 2001-261720

[0011] Patent Document 3: JP-A No. 2021-91228

[0012] Patent Document 4: International Publication No. WO2007 / 055361

[0013] Non-patent literature

[0014] Non-patent document 1: “Liquid phase adsorption characteristics of metal-supported porous carbon for removal of sulfur-based impurities from bioethanol”, The Society of Chemical Engineers of Japan (SCEJ), Proceedings of SCEJ Annual Meeting, 2009, p. 216 Summary of the invention

[0015] Problem that the invention aims to solve

[0016] As described above, propylene-based polymers are widely used as industrial sheets, automobile components, etc. due to their excellent properties. On the other hand, from the viewpoint of environmental protection, it is required to reduce the amount of raw materials derived from fossil resources used in the production process of propylene-based polymers as much as possible.

[0017] However, since compounds derived from biomass raw materials contain impurities and foreign substances, there is a concern that degradation of the quality of the final product may occur when used or interference with long-term continuous production may occur.

[0018] In view of the above-mentioned problems of the prior art, an object of the present invention is to provide a method for producing a propylene-based polymer, wherein even when a biomass-derived reaction inhibitor containing impurities is used in the production of the propylene-based polymer, the propylene-based polymer can be produced without causing a significant decrease in productivity and long-term operational instability due to the formation of blocky resins.

[0019] Solutions for solving problems

[0020] As a result of intensive research, the inventors of the present disclosure have found that the impurities contained in the reaction inhibitor derived from the biomass raw material fall within a certain range, and the reaction inhibitor can be applied to polypropylene polymerization without causing problems such as reduction in catalytic activity, formation of blocky resins, and changes in color and odor. Based on these findings, the inventors of the present disclosure have finally completed the present invention.

[0021] The present invention relates to the following methods [1] to [7] for producing propylene-based polymers.

[0022] [1] A method for producing a propylene polymer,

[0023] wherein, in the first step, a propylene homopolymer or a copolymer of propylene and at least one monomer selected from the group consisting of α-olefins having 2 to 10 carbon atoms other than propylene is produced as the first propylene-based polymer using one or more polymerization reactors in the presence of an olefin polymerization catalyst;

[0024] wherein, in the subsequent second step, a propylene homopolymer or a copolymer of propylene and at least one monomer selected from the group consisting of α-olefins having 2 to 10 carbon atoms other than propylene is produced as the second propylene-based polymer using one or more polymerization reactors in the presence of the first propylene-based polymer; and

[0025] At least one selected from the group consisting of the first step, the second step, and between the first step and the second step includes adding a biomass-derived reaction inhibitor containing 5 to 2000 ppm by mass of water.

[0026] [2] The method for producing a propylene-based polymer according to the above-mentioned [1], wherein the reaction inhibitor further contains 0.1 mass ppm to 1000 mass ppm of methanol.

[0027] [3] The method for producing a propylene-based polymer according to [1] or [2] above, wherein the reaction inhibitor further contains 0.1 to 5 ppm by mass of sulfur atoms and 0.1 to 100 ppb by mass of copper atoms.

[0028] [4] The method for producing a propylene-based polymer according to any one of [1] to [3] above, wherein the reaction inhibitor is biomass-derived ethanol.

[0029] [5] The method for producing a propylene-based polymer according to any one of [1] to [4] above, wherein the olefin polymerization catalyst comprises a solid catalyst component (A) comprising the following (A1), (A2) and (A3) and optionally comprising the following (A4) and the following component (B):

[0030] (A1) A solid component comprising magnesium, titanium, a halogen and an electron-donating compound serving as an internal donor

[0031] (A2) Organic aluminum compounds

[0032] (A3) Organic silicon compounds other than vinylsilane compounds

[0033] (A4) Vinylsilane compound

[0034] (B) Organic aluminum compounds.

[0035] [6] The method for producing a propylene-based polymer according to any one of [1] to [5] above, wherein the second propylene-based polymer produced in the second step is a copolymer of propylene and at least one monomer selected from the group consisting of α-olefins containing 2 to 10 carbon atoms other than propylene, and the content of at least one monomer selected from the group consisting of α-olefins containing 2 to 10 carbon atoms other than propylene is in the range of 20% by mass to 80% by mass.

[0036] [7] The method for producing a propylene-based polymer according to the above [5] or [6], wherein the amount of the reaction inhibitor added is 0.01 g to 30 g relative to 1 g of the total amount of the solid catalyst component (A).

[0037] Effects of the Invention

[0038] According to the present invention, a continuous multi-stage production method of a propylene-based polymer can be provided, which is configured to produce a propylene-based polymer without causing an excessive decrease in catalytic polymerization activity and instability in continuous production due to the formation of blocky resins even when a reaction inhibitor derived from a biomass raw material is used. DETAILED DESCRIPTION

[0039] The method for producing a propylene-based polymer of the present invention is the following method for producing a propylene-based polymer:

[0040] wherein, in the first step, a propylene homopolymer or a copolymer of propylene and at least one monomer selected from the group consisting of α-olefins having 2 to 10 carbon atoms other than propylene is produced as the first propylene-based polymer using one or more polymerization reactors in the presence of an olefin polymerization catalyst;

[0041] wherein, in the subsequent second step, a propylene homopolymer or a copolymer of propylene and at least one monomer selected from the group consisting of α-olefins having 2 to 10 carbon atoms other than propylene is produced as the second propylene-based polymer using one or more polymerization reactors in the presence of the first propylene-based polymer; and

[0042] At least one selected from the group consisting of the first step, the second step, and between the first step and the second step includes adding a biomass-derived reaction inhibitor containing 5 to 2000 ppm by mass of water.

[0043] In the present invention, a biomass-derived reaction inhibitor containing 5 to 2000 ppm by mass of water is added to at least one of the groups selected from the first step, the second step, and the first step and the second step. Therefore, while suppressing excessive reduction in polymerization catalytic activity and not causing long-term operational instability due to the formation of blocky resins, the desired propylene polymer can be produced while reducing environmental load. By using a reaction inhibitor derived from a biomass raw material containing impurities within a specific concentration as a substitute for a reaction inhibitor derived from fossil resources, the desired propylene polymer can be produced while reducing environmental load.

[0044] Hereinafter, an embodiment of the present invention will be described in detail. The description of the constituent elements described below is only an example of an embodiment of the present invention, and the present invention is not limited to the contents described below unless it exceeds the gist of the present invention.

[0045] In the present specification, "to (-)" indicating a numerical range means a numerical range including the numerical values ​​described before and after "to (-)" as the lower limit and the upper limit.

[0046] I. Production method of propylene polymer

[0047] 1. Polymerization Step

[0048] In the production method of the present invention, in which, in the first step, a first propylene-based polymer is polymerized using one or two or more polymerization reactors and in the presence of a catalyst for olefin polymerization described later, and in the subsequent second step, a second propylene-based polymer is polymerized using one or two or more polymerization reactors and in the presence of the first propylene-based polymer, a biomass-derived reaction inhibitor containing at least 5 mass ppm to 2000 mass ppm of moisture as an impurity is added to at least one selected from the group consisting of the first step, the second step, and the step between the first and second steps.

[0049] The polymerization method of the production method of the present invention can use any known method such as bulk polymerization, gas phase polymerization, solution polymerization and slurry polymerization, as long as the olefin polymerization catalyst is effectively contacted with the monomer. From an economic point of view, the most preferred is a gas phase polymerization method, in which the monomer is kept in a gaseous form without substantially using a liquid solvent, thereby improving the production efficiency per unit catalyst. As a polymerization method, a continuous or intermittent polymerization method is used.

[0050] The number of polymerization reactors may be 1 or 2 or more in both the first step and the second step. The first step is carried out in 1 or 2 or more gas phase polymerization reactors, and the second step is carried out in 1 or 2 or more gas phase polymerization reactors. When several polymerization reactors are used, they may be connected in series or in parallel.

[0051] As the gas phase polymerization reactor, examples include, but are not limited to, a fluidized bed reactor and a horizontal reactor equipped with a stirrer rotating about a horizontal axis therein.

[0052] As the monomer used for the polymerization in the first step or the second step, in the case of producing a propylene homopolymer, a single propylene monomer is used.

[0053] In the case of producing a copolymer of propylene and at least one monomer selected from the group consisting of α-olefins containing 2 to 10 carbon atoms other than propylene, a monomer mixture in which at least one comonomer selected from the group consisting of ethylene and α-olefins containing 4 to 10 carbon atoms is introduced into propylene is used as a monomer and as a raw material in step 1 or step 2. As the α-olefin containing 4 to 10 carbon atoms, examples include, but are not limited to, 1-butene, 1-pentene, 4-methyl-1-pentene, 3-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, and 1-decene.

[0054] The polymerization temperature is preferably 0° C. to 90° C., more preferably 30° C. to 85° C., and still more preferably 45° C. to 80° C. The polymerization pressure is preferably 0.1 MPaG to 5 MPaG, and more preferably 0.5 MPaG to 4 MPaG.

[0055] Generally, by selecting a higher temperature and a higher pressure, productivity per gram of catalyst can be improved; however, on the other hand, local heating cannot be eliminated, and fine powder is generated due to the collapse of growing particles, or aggregates or agglomerates are formed due to fusion. Therefore, considering the balance between productivity per gram of catalyst and elimination of local heating, the polymerization temperature and the polymerization pressure are adjusted within the above-mentioned temperature range and pressure range, respectively.

[0056] The residence time can be arbitrarily adjusted according to the composition of the polymerization reactor. Usually, it is set in the range of 30 minutes to 10 hours. The residence time is preferably less than 4 hours, and more preferably less than 3 hours. Usually, by selecting a longer residence time, the productivity of each gram of catalyst can be improved. However, when the residence time is too long, the rate of increase of the productivity of each gram of catalyst relative to the increase of the residence time is reduced. Therefore, considering the productivity of each gram of catalyst, the residence time is adjusted within the above range.

[0057] In the method for producing a propylene-based polymer of the present invention, from the viewpoint of productivity, in the first step, 10,000 g or more of the first propylene-based polymer is preferably produced per gram of the olefin polymerization catalyst described later.

[0058] 2. Reaction inhibitors derived from biomass

[0059] As the biomass-derived reaction inhibitor in the present invention, at least one of an alcohol compound and a compound containing ethylene glycol can be used. From the viewpoint of reducing the environmental load, the reaction inhibitor is preferably an agent that can be synthesized from a biomass raw material, and particularly preferably an agent that can be synthesized from a plant-derived raw material. This is because plants absorb and consume carbon dioxide through photosynthesis during growth. Among the biomass-derived reaction inhibitors, it is more preferred that an alcohol compound or a compound containing ethylene glycol can be synthesized using bioethylene produced by plants as a starting material.

[0060] From the viewpoint of relatively high safety to the human body and easy handling during production, alcohol compounds are most preferred.

[0061] In the present invention, whether the reaction inhibitor is derived from biomass can be determined by using known methods such as 14 C and 18 Methods for measuring biobasicity of isotopes such as O (e.g., ASTM D6866, carbon isotope 14 When isotopes are present, the reaction inhibitor can be judged as a biomass-derived agent. For example, in order to distinguish between ethanol derived from biomass and ethanol derived from petrochemical products, it is possible to use a method that measures hydrogen isotopes D or oxygen isotopes D using isotope ratio mass spectrometry (IRMS) or the like. 18 O content method.

[0062] 2-1. Alcohol compounds derived from biomass

[0063] The biomass-derived alcohol compound used in the reaction inhibitor of the present invention may be, for example, a compound represented by the following general formula (1).

[0064] [General formula (1)]

[0065] HO-R 1

[0066] (where R 1 represents a saturated hydrocarbon group containing 2 to 10 carbon atoms. )

[0067] Among the alcohol compounds represented by the general formula (1), a saturated hydrocarbon group containing 2 to 10 carbon atoms can be selected as R from the viewpoint of removal by drying. 1 A preferred example of R 1 More preferred is a saturated hydrocarbon group containing 2 to 8 carbon atoms, and still more preferred is a saturated hydrocarbon group containing 2 to 3 carbon atoms.

[0068] When R 1 When the carbon number of the carbon atoms is greater than 10, removal by drying becomes difficult and there is a high possibility that the final product has problems such as odor.

[0069] The biomass-derived alcohol compound is most preferably ethanol containing 2 carbon atoms (bioethanol) which is widely produced from biomass raw materials.

[0070] 2-2. Biomass-derived compounds containing ethylene glycol

[0071] The biomass-derived compound containing ethylene glycol used in the reaction inhibitor of the present invention may be, for example, a compound represented by the following general formula (2) or the following general formula (3).

[0072] [General formula (2)]

[0073] HO-[CH2-CH2-O] p -R 2

[0074] (where p is an integer and satisfies 1≤p≤10, and R 2 represents a hydrogen atom or a hydrocarbon group containing 1 to 25 carbon atoms. )

[0075] Since the polyoxyethylene backbone has high hydrophilicity, when p increases, there may be limitations on handling during production, such as reduced solubility in organic solvents and solidification at room temperature. Therefore, 1≤p≤10 may be preferably selected.

[0076] More specifically, as the compound containing ethylene glycol derived from biomass, examples include, but are not limited to, ethylene glycol, diethylene glycol, polyoxyethylene (3) lauryl ether, polyoxyethylene (4) lauryl ether, polyoxyethylene (5) lauryl ether, polyoxyethylene (3) stearyl ether, polyoxyethylene (4) stearyl ether, polyoxyethylene (5) stearyl ether, polyoxyethylene (4) oleyl ether, and polyoxyethylene (6) oleyl ether. The numerical values ​​in parentheses represent the degree of polymerization of the polyoxyalkylene.

[0077] [General formula (3)]

[0078] HO-[CH2-CH(R 3 )-O] l -[CH2-CH(R 4 )-O] m -[CH2-CH(R 5 )-] n -H

[0079] (where l, m and n are integers and satisfy all of the following relations: 0≤l≤70, 0≤m≤70, 0≤n≤70 and 2≤l+m+n; R 3 , R 4 and R 5 Each independently represents a hydrogen atom or a hydrocarbon group containing 1 to 5 carbon atoms; and a hydrogen atom is selected as R 3 , R 4 and R 5 and when several hydrocarbon groups are selected, they may be the same as or different from each other.

[0080] When R 3 , R 4 and R 5 When each is independently a hydrogen atom, that is, when it is polyoxyethylene, since the polyoxyethylene skeleton has high hydrophilicity and crystallinity, the increase in its abundance may limit the operation during production, such as reduced solubility in organic solvents and solidification at room temperature. Therefore, 70 can be preferably selected as the upper limit of the degree of polymerization of polyoxyethylene, that is, the upper limit of l, m and n.

[0081] When R 3 , R 4 and R 5 When each is independently a hydrocarbon group, there is a possibility that the molecular weight increases with the number of carbon atoms, resulting in an increase in viscosity and a decrease in affinity for solvents and causing restrictions on handling.

[0082] Therefore, 5 can be preferably selected as the upper limit of the number of carbon atoms. 3 , R 4 and R 5 When each is independently a hydrocarbon group, the most preferred is one in which R3 , R 4 and R 5 Each contains propylene oxide of 1 carbon atom.

[0083] Examples of such compounds include, but are not limited to, polyoxyethylene (1) polyoxypropylene (16) polyoxyethylene (1), polyoxyethylene (2) polyoxypropylene (16) polyoxyethylene (2), polyoxyethylene (2) polyoxypropylene (30) polyoxyethylene (2), polyoxyethylene (6) polyoxypropylene (35) polyoxyethylene (6), polyoxyethylene (5) polyoxypropylene (69) polyoxyethylene (5), polyoxyethylene (3) polyoxypropylene (2) polyoxyethylene (3) lauryl ether, polyoxyethylene (3) polyoxypropylene (3) lauryl ether, polyoxypropylene (26) polyoxyethylene (6), polyoxypropylene (26), polyoxypropylene (26) polyoxyethylene (7), polyoxypropylene (26), polyoxypropylene (22) polyoxyethylene (6), polyoxypropylene (22), polyoxypropylene (12) polyoxyethylene (14), and polyoxypropylene (12). The numerical values ​​in parentheses represent the degree of polymerization of the polyoxyalkylene.

[0084] The compound containing ethylene glycol used in the biomass-derived reaction inhibitor of the present invention may be a single component or a mixture of a plurality of components.

[0085] Furthermore, the biomass-derived reaction inhibitor may be one type of reaction inhibitor, may be a mixture of two or more types of reaction inhibitors, or may be a mixture of an alcohol compound and a compound containing ethylene glycol.

[0086] 3. Impurities in biomass-derived reaction inhibitors

[0087] As impurities contained in the biomass-derived reaction inhibitor of the present invention, examples include, but are not limited to, water, methanol, sulfur compounds, and copper compounds.

[0088] For example, in the case of alcohols produced from biological resources by fermentation such as bioethanol, as impurities, examples include, but are not limited to, water, methanol, sulfur compounds such as dimethyl sulfide, and copper compounds such as copper acetate that may be mixed during the production process.

[0089] The content of water in the biomass-derived reaction inhibitor is preferably in the range of 5 mass ppm to 2000 mass ppm. The lower limit may be 20 mass ppm or more, may be greater than 100 mass ppm, may be 200 mass ppm or more, or may be 500 mass ppm or more. The upper limit may be 1800 mass ppm or less, or it may be 1700 mass ppm or less.

[0090] When a mixture of two or more reaction inhibitors is used, the total water content in the reaction inhibitor is adjusted within the above range, for example, within a range of 5 mass ppm to 2000 mass ppm.

[0091] When the moisture content is higher than this range, there is a production problem in which moisture accumulates within production equipment and induces equipment failure.

[0092] When the moisture content is lower than this range, it means that energy for impurity removal is used according to the degree of purification. Therefore, even when the reaction inhibitor is derived from biomass, the advantage in terms of environmental load is weakened.

[0093] From the viewpoint of ensuring safety for human body when operating in the propylene polymer production process and suppressing odor and improving product safety by reducing the residual amount in the final product, the content of methanol as an impurity in the biomass-derived reaction inhibitor is preferably in the range of 0.1 mass ppm to 1000 mass ppm. Regarding the content of methanol as an impurity in the biomass-derived reaction inhibitor, the lower limit may be 30 mass ppm or more, may be 100 mass ppm or more, may be greater than 200 mass ppm, or may be 300 mass ppm or more. The upper limit may be 700 mass ppm or less, or it may be 500 mass ppm or less.

[0094] From the viewpoint of suppressing changes in quality such as odor and color of the product, the content of sulfur atoms as impurities in the biomass-derived reaction inhibitor is preferably in the range of 0.1 to 5 ppm by mass.

[0095] Regarding the content of sulfur atoms as impurities in the biomass-derived reaction inhibitor, the lower limit may be 0.2 mass ppm or more, or it may be 0.3 mass ppm or more. The upper limit may be 4 mass ppm or less, or it may be 3 mass ppm or less.

[0096] When the sulfur atom content is lower than this range, energy for impurity removal is required depending on the degree of purification. Therefore, even when the reaction inhibitor is derived from a biomass raw material, the advantage in terms of environmental load is reduced.

[0097] From the viewpoint of reducing the possibility of quality degradation due to by-products accidentally mixed into the product, the content of copper atoms as impurities in the biomass-derived reaction inhibitor is preferably in the range of 0.1 mass ppb to 100 mass ppb. This is because an oxidation reaction using copper ions as active sites may occur as a side reaction.

[0098] Regarding the content of copper atoms as impurities in the biomass-derived reaction inhibitor, the lower limit may be 1 mass ppm or more, or it may be 10 mass ppm or more. The upper limit may be 70 mass ppm or less, or it may be 60 mass ppm or less.

[0099] When the copper atom content is lower than this range, energy for impurity removal is required depending on the degree of purification. Therefore, even when the reaction inhibitor is derived from a biomass raw material, the advantage in terms of environmental load is reduced.

[0100] The biomass-derived reaction inhibitor used in the present invention is preferably a reaction inhibitor that does not leave any substance on the paper when filtered through filter paper No. 5C specified in JIS P 3801.

[0101] As the biomass-derived reaction inhibitor used in the present invention, at least one may be appropriately selected from commercially available biomass-derived alcohol compounds and compounds containing ethylene glycol.

[0102] If the content of impurities contained in at least one of the commercially available alcohol compounds derived from biomass and compounds containing ethylene glycol exceeds the content of impurities specified in the present invention, the selected compound may be refined before using the selected compound so that the content of impurities in the compound is within the specified content. A biomass-derived reaction inhibitor having a moisture content exceeding 2000 mass ppm may be passed through a column filled with, for example, molecular sieves 3A or 4A (e.g., available from Resonac Corporation) to reduce the moisture content to within the range of 5 mass ppm to 2000 mass ppm, and then the reaction inhibitor may be used as a biomass-derived reaction inhibitor used in the present invention.

[0103] 4. Supply of reaction inhibitor

[0104] The reaction inhibitor is supplied in at least one selected from the group consisting of the first step, the second step, and between the first step and the second step. From the viewpoint of suppressing a significant decrease in catalytic activity, the reaction inhibitor is preferably supplied at least between the first step and the second step.

[0105] The method for supplying the reaction inhibitor in at least one selected from the group consisting of the first step, the second step, and between the first step and the second step is preferably any of the following supply methods.

[0106] (4-1) A method of using only one compound as a reaction inhibitor and supplying it alone to a polymerization reactor.

[0107] (4-2) A method of using two or more compounds as reaction inhibitors and supplying them to the polymerization reactor from different supply lines.

[0108] (4-3) A method of using several compounds as reaction inhibitors, premixing an alcohol compound and a compound containing polyethylene glycol, supplying the mixture as a mixed reaction inhibitor to a polymerization reactor through a supply line, and optionally supplying oxygen to the polymerization reactor from a different supply line.

[0109] (4-4) A method of using several compounds as reaction inhibitors, supplying an alcohol compound and a compound containing polyethylene glycol from different supply lines and mixing them in the supply lines, feeding the mixture to a polymerization reactor, and optionally supplying oxygen from a different supply line to the polymerization reactor.

[0110] Compounds containing ethylene glycol generally have high viscosity. Therefore, it is economically disadvantageous to supply compounds containing ethylene glycol alone because more energy is required due to pressure loss in the piping. Therefore, in the case of using compounds containing ethylene glycol, method (4-3) or (4-4) is preferred.

[0111] However, this is not applicable unless a compound containing ethylene glycol is used as a reaction inhibitor. Among them, (4-2) or (4-1) in which each supply amount can be independently controlled is a preferred method.

[0112] The position of the polymerization reactor for supplying the reaction inhibitor may be any position when the gas phase polymerization reactor is a mixing tank type reactor, and is preferably on the upstream side when the polymerization reactor is a plug flow type reactor.

[0113] The amount of the reaction inhibitor supplied may be any amount that makes the productivity of each polymerization step a desired value. When the reaction inhibitor is supplied to the first step, it is preferred to supply the reaction inhibitor so that the total amount of the reaction inhibitor supplied is in the range of 0.01 g to 10 g relative to 1 gram of the solid catalyst component (A) described below. The total amount is more preferably 0.5 g or more, still more preferably 1 g or more, and most preferably 3 g or more. The total amount may be 8 g or less, or it may be 5 g or less.

[0114] When the reaction inhibitor is supplied to the second step, the amount of the reaction inhibitor supplied may be any amount that makes the productivity of each polymerization step a desired value, as described above. The reaction inhibitor is preferably supplied so that the total amount of the reaction inhibitor supplied is in the range of 10 mass % to 90000 mass %, and more preferably so that the total amount of the reaction inhibitor supplied is in the range of 2000 mass % to 85000 mass %, relative to the titanium in the solid catalyst component (A) supplied to the first step.

[0115] When the reaction inhibitor is supplied between the first step and the second step, the amount of the reaction inhibitor supplied may be any amount that makes the productivity of each polymerization step a desired value, as described above. The reaction inhibitor is preferably supplied so that the total amount of the reaction inhibitor supplied is in the range of 10 mass % to 90000 mass %, and more preferably so that the total amount of the reaction inhibitor supplied is in the range of 2000 mass % to 85000 mass %, relative to the titanium in the solid catalyst component (A) supplied to the first step.

[0116] In addition, it is preferred to add a reaction inhibitor so that the total amount of the reaction inhibitor added is in the range of 0.01g to 30g relative to the total amount 1g of the solid catalyst component (A) described later. Relative to the total amount 1g of the solid catalyst component (A) described later, the total amount of the reaction inhibitor added is more preferably 0.5g or more, still more preferably 1g or more, and most preferably 3g or more. The total amount can be 20g or less, or it can be 10g or less. "Total amount 1g of solid catalyst component (A)" does not include the prepolymerized polymer described later.

[0117] When the total amount of the reaction inhibitor satisfies the above ratio, the surface of the propylene-based polymer particles can be moderately deactivated. Therefore, the stickiness of the particles widely caused by producing a component with a high comonomer content can be suppressed, and there is an advantage that the formation of bulk polymers due to the stickiness of the particles can be suppressed and the contamination of the reactor wall surface due to the particles attached to the reactor wall surface can be prevented.

[0118] The present invention does not limit the use of reaction inhibitors other than reaction inhibitors derived from biomass. Reaction inhibitors other than reaction inhibitors derived from biomass may be further included to the extent that the effect of the present invention is not significantly hindered. As reaction inhibitors other than reaction inhibitors derived from biomass, examples include, but are not limited to, reaction inhibitors derived from petrochemical products. However, from the viewpoint of improving the effect of the present invention, the reaction inhibitor derived from biomass can be 50% by mass or more, 70% by mass or more, 90% by mass or more, or 100% by mass, relative to the total amount of the reaction inhibitor used in the present invention.

[0119] II. Catalysts for olefin polymerization

[0120] The olefin polymerization catalyst used in the present invention is preferably a so-called Ziegler catalyst comprising components (A) and (B) as constituent components, component (A) being a solid catalyst component comprising magnesium, titanium, a halogen and an electron-donating compound serving as an internal donor, and component (B) being an organic aluminum compound.

[0121] From the viewpoint of suppressing a significant decrease in catalytic activity caused by a reaction inhibitor, the catalyst for olefin polymerization preferably comprises: a solid catalyst component (A) comprising the following (A1), (A2) and (A3) and optionally comprising the following (A4), and the following component (B):

[0122] (A1) A solid component comprising magnesium, titanium, a halogen and an electron-donating compound serving as an internal donor

[0123] (A2) Organic aluminum compounds

[0124] (A3) Organic silicon compounds other than vinylsilane compounds

[0125] (A4) Vinylsilane compound

[0126] (B) Organic aluminum compounds.

[0127] 1. Component (A): solid catalyst component

[0128] As the solid catalyst component comprising magnesium, titanium, halogen and an electron donating compound serving as an internal donor, conventionally known solid catalyst components can be used. In addition to the above 4 components, the solid catalyst component may contain any component in any form to the extent that the effects of the present invention are not impaired.

[0129] (A1a: magnesium source)

[0130] As the magnesium source of the solid catalyst component, any magnesium compound can be used. Representative examples of the magnesium compound are the compounds disclosed in JP-A No. H03-234707.

[0131] In general, the following can be used as the magnesium source: magnesium halide compounds represented by magnesium chloride, alkoxymagnesium compounds represented by diethoxymagnesium, metallic magnesium, oxymagnesium compounds represented by magnesium oxide, hydroxymagnesium compounds represented by magnesium hydroxide, Grignard compounds represented by butylmagnesium chloride, organic magnesium compounds represented by butylethylmagnesium, magnesium salt compounds of inorganic or organic acids represented by magnesium carbonate and magnesium stearate, mixtures thereof, and compounds having an average composition formula of the formula formed by mixing them (e.g., Mg(OEt) m Cl 2-m The compound represented by <m<2)。

[0132] Among them, preferred are magnesium chloride, diethoxymagnesium, metallic magnesium and butylmagnesium chloride.

[0133] (A1b: titanium source)

[0134] As the titanium source of the solid catalyst component, any titanium compound can be used. Representative examples of the titanium compound are the compounds disclosed in JP-A No. H03-234707. Regarding the valence of titanium, a titanium compound having any valence of tetravalent, trivalent, divalent or zero-valent can be used. Preferably, a tetravalent or trivalent titanium compound is used, and more preferably a tetravalent titanium compound.

[0135] Examples of the tetravalent titanium compound include, but are not limited to, titanium halide compound classes represented by titanium tetrachloride, alkoxy titanium compound classes represented by tetrabutoxy titanium, alkoxy titanium condensation compound classes having a Ti-O-Ti bond represented by tetrabutoxy titanium dimer (BuO)3Ti-O-Ti(OBu)3, and organometallic titanium compound classes represented by dicyclopentadienyl titanium dichloride. Among them, titanium tetrachloride and tetrabutoxy titanium are particularly preferred.

[0136] Examples of the trivalent titanium compound include, but are not limited to, titanium halide compound classes represented by titanium trichloride. As the titanium trichloride, a compound produced by any known method can be used, such as a hydrogen reduction type compound, a metal aluminum reduction type compound, a metal titanium reduction type compound, and an organoaluminum reduction type compound.

[0137] The above titanium compounds can be used alone or in combination of multiple compounds. In addition, a mixture of the above titanium compound classes, a compound having an average composition formula formed by mixing them (for example, a compound represented by Ti(OBu) m Cl 4-m where 0 < m < 4), or a complex with other compounds such as phthalic acid esters (for example, a compound represented by Ph(CO2Bu)2·TiCl4) can be used.

[0138] (A1c: halogen)

[0139] The halogen in the solid catalyst component can be fluorine, chlorine, bromine, iodine or a mixture thereof. Among them, chlorine is preferred.

[0140] As the halogen source of the solid catalyst component, usually any of the above magnesium halides and titanium halides is used. In addition, other halogen sources can also be used, such as known halogen compounds, such as aluminum halides (for example, AlCl3, AlBr3, AlI3), boron halides (for example, BCl3, BBr3, BI3), silicon halides (for example, SiCl4), phosphorus halides (for example, PCl3, PCl5), tungsten halides (for example, WCl6) and molybdenum halides (for example, MoCl5).

[0141] (A1d: electron-donating compound used as internal donor)

[0142] In polymerization techniques using Ziegler catalysts, internal and external donors are generally considered to have different functions.

[0143] The internal donor is a donor used simultaneously when the titanium compound is supported on the magnesium compound to form an active site, and controls the position where the titanium atom is coordinated and changes the electronic state of the coordinated titanium atom.

[0144] At the same time, the external donor changes the properties of the active sites that have been formed. For example, by further using the external donor in the prepared solid catalyst component, the active sites that have been formed can be changed to highly stereospecific active sites, and the active sites that can produce non-crystalline components can be poisoned. Therefore, a propylene-based polymer with higher stereoregularity and less non-crystalline components can be produced.

[0145] As the electron donating compound (internal donor), examples include, but are not limited to, oxygen-containing electron donating compounds such as alcohols, phenols, ketones, aldehydes, carboxylic acids, esters of organic acids or inorganic acids, ethers, amides and anhydrides; nitrogen-containing electron donating compounds such as ammonia, amines, nitriles and isocyanates; and sulfur-containing electron donating compounds such as sulfonic acid esters. In particular, examples include, but are not limited to, compounds described in paragraph 0037 of JP-A No. 2010-70584.

[0146] Among them, the following compounds are preferred: for example, phthalate compounds represented by diethyl phthalate, di-n-butyl phthalate, diisobutyl phthalate and diheptyl phthalate; phthalate halide compounds represented by dichlorophthalic acid; malonate compounds having one or two substituents at the 2-position (for example, 2-n-butyl diethyl malonate); phthalate compounds having one or two substituents at the 2-position or one or more substituents at the 2-position and the 3-position. Succinate compounds having a substituent (for example, 2-n-butyl diethyl succinate); aliphatic polyether compounds having one or two substituents at the 2-position, represented by 1,3-dimethoxypropane (for example, 2-isopropyl-2-isobutyl-1,3-dimethoxypropane, 2-isopropyl-2-isopentyl-1,3-dimethoxypropane); and polyether compounds containing an aromatic free radical in the molecule, represented by 9,9-bis(methoxymethyl)fluorene.

[0147] These electron donating compounds may be used alone or in combination of plural compounds.

[0148] The solid catalyst component of the present invention can be prepared by contacting a magnesium compound, a titanium compound, a halogen compound and an electron donating compound serving as an internal donor with each other to form a solid component (A1) containing magnesium, titanium, halogen and an electron donating compound serving as an internal donor.

[0149] The amount of the titanium compound used is preferably in the range of 0.0001 to 1,000, and particularly preferably in the range of 0.01 to 10 in terms of a molar ratio to the amount of the magnesium compound used (ie, the number of moles of the titanium compound / the number of moles of the magnesium compound).

[0150] When a halogen compound is used in addition to the magnesium compound and the titanium compound, regardless of whether the magnesium compound and the titanium compound contain halogen, the amount of the halogen compound used is preferably in the range of 0.01 to 1,000 in terms of a molar ratio to the amount of the magnesium compound used (i.e., the number of moles of the halogen compound / the number of moles of the magnesium compound), and particularly preferably in the range of 0.1 to 100.

[0151] The amount of the electron donating compound used as the internal donor is preferably in the range of 0.001 to 10, and particularly preferably in the range of 0.01 to 5, in terms of molar ratio to the amount of the magnesium compound used (ie, moles of the electron donating compound / moles of the magnesium compound).

[0152] After the solid component (A1) is formed, the solid catalyst component may be further contacted with an organoaluminum compound (A2), an organosilicon compound (A3) other than a vinylsilane compound, a vinylsilane compound (A4), etc. For example, after the solid component (A1) is formed, the solid catalyst component may be further contacted with an organoaluminum compound (A2) and an organosilicon compound (A3) other than a vinylsilane compound, or after the solid component (A1) is formed, the solid catalyst component may be further contacted with an organoaluminum compound (A2), an organosilicon compound (A3) other than a vinylsilane compound, and a vinylsilane compound (A4).

[0153] The solid catalyst component (A) comprising (A1), (A2) and (A3) and optionally comprising the following (A4) can suppress a significant decrease in catalytic activity caused by a reaction inhibitor.

[0154] (A2: Organic aluminum compounds)

[0155] As the organoaluminum compound (A2) used in the solid catalyst component of the present invention, a compound represented by the following general formula (4) is preferably used.

[0156] [General formula (4)]

[0157] R 6s AlX t (OR 7 ) u

[0158] (where R 6 is a hydrocarbon group; X is a halogen or a hydrogen atom; R 7 is a hydrocarbon group containing 1 to 20 carbon atoms or a crosslinking group formed by Al; s, t and u satisfy 1≤s≤3, 0≤t<2 and 0≤u≤2 respectively; and s, t and u satisfy s+t+u=3. )

[0159] In the general formula (4), R 6 It is preferably a hydrocarbon group containing 1 to 10 carbon atoms, more preferably a hydrocarbon group containing 1 to 8 carbon atoms, and particularly preferably a hydrocarbon group containing 1 to 6 carbon atoms. 6 Examples include, but are not limited to, methyl, ethyl, propyl, butyl, isobutyl, hexyl and octyl. Among them, methyl, ethyl and isobutyl are most preferred.

[0160] In the general formula (4), X is a halogen or a hydrogen atom. Examples of the halogen that can be used as X include, but are not limited to, fluorine, chlorine, bromine, and iodine. Among them, chlorine is particularly preferred.

[0161] In the general formula (4), R 7 is a hydrocarbon group containing 1 to 20 carbon atoms or a crosslinking group formed by Al. 7 When it is a hydrocarbon group, R 7 Can be selected from the above as R 6 The exemplified hydrocarbon groups are the same group.

[0162] In addition, as the organic aluminum compound, an aluminoxane compound represented by methylaluminoxane can be used. In this case, R 7 represents a cross-linking group formed by Al.

[0163] The crosslinking group formed by Al means that two or more groups each having R removed from the general formula (4) 7 The residue of the structure of cross-linked aluminum atoms, or it represents the hydrocarbon group and having R removed from the general formula (4) 7 The residues of the structure are cross-linked by aluminum atoms.

[0164] As the organoaluminum compound, examples include, but are not limited to, the following: (a) trialkylaluminums, such as trimethylaluminum, triethylaluminum, triisobutylaluminum, tri-n-hexylaluminum, tri-n-octylaluminum, and tri-n-decylaluminum, (b) alkylaluminum halides, such as diethylaluminum monochloride, diisobutylaluminum monochloride, sesquiethylaluminum chloride, and ethylaluminum dichloride, (c) alkylaluminum hydrides, such as diethylaluminum hydride and diisobutylaluminum hydride, and (d) alkylaluminum alkoxides, such as diethylethoxyaluminum and diethylphenoxyaluminum. Among them, triethylaluminum and triisobutylaluminum are preferred.

[0165] As the organoaluminum compound, a single compound may be used, or several compounds may be used in combination.

[0166] The amount of the organoaluminum compound used is preferably in the range of 0.1 to 100, and particularly preferably in the range of 1 to 50, in terms of the atomic ratio of aluminum to titanium (ie, the number of moles of aluminum atoms / the number of moles of titanium atoms).

[0167] (A3: Organic silicon compounds other than vinylsilane compounds)

[0168] As the organic silicon compound other than the vinylsilane compound used in the solid catalyst component of the present invention, for example, compounds disclosed in JP-A No. 2004-124090 can be used, and alkoxysilane compounds are preferred.

[0169] As the alkoxysilane compound, a compound represented by the following general formula (5) is preferably used.

[0170] [General formula (5)]

[0171] R 8 R 9 f Si(OR 10 ) g

[0172] (where R 8 represents a hydrocarbon group or a hydrocarbon group containing a heteroatom; R 9 represents a hydrogen atom, a halogen, a hydrocarbon group, or a hydrocarbon group containing a heteroatom; R 10 represents a hydrocarbon group; f and g are values ​​satisfying 0≤f≤2 and 1≤g≤3, respectively; and f and g are values ​​satisfying f+g=3. )

[0173] In the general formula (5), R 8 It represents a hydrocarbon group or a hydrocarbon group containing a heteroatom.

[0174] When R 8 When it is a hydrocarbon group, it is usually a hydrocarbon group containing 1 to 20 carbon atoms, and preferably a hydrocarbon group containing 3 to 10 carbon atoms. 8Examples include, but are not limited to, straight-chain aliphatic hydrocarbon groups represented by n-propyl, branched aliphatic hydrocarbon groups represented by isopropyl and tert-butyl, alicyclic hydrocarbon groups represented by cyclopentyl and cyclohexyl, and aromatic hydrocarbon groups represented by phenyl. 8 , a branched aliphatic hydrocarbon group or an alicyclic hydrocarbon group is more preferably used, and isopropyl, isobutyl, tert-butyl, hexyl (1,1,2-trimethylpropyl), cyclopentyl or cyclohexyl or the like is particularly preferably used.

[0175] When R 8 In the case of a hydrocarbon group containing a hetero atom, the hetero atom is preferably selected from nitrogen, oxygen, sulfur, phosphorus and silicon, and the hetero atom is particularly preferably nitrogen or oxygen. 8 The skeleton structure of the hydrocarbon group containing heteroatoms is preferably selected from the above-mentioned 8 The above are those exemplified in the case of the hydrocarbon group. Among them, N,N-diethylamino, quinolyl or isoquinolyl is particularly preferred.

[0176] When R 8 In the case of a hydrocarbon group containing a hetero atom, the hydrocarbon group containing a hetero atom may be bonded to Si via any of the carbon atom and the hetero atom constituting the hydrocarbon group containing a hetero atom.

[0177] In the general formula (5), R 9 represents a hydrogen atom, a halogen atom, a hydrocarbon group, or a hydrocarbon group containing a heteroatom. 9 Examples of the halogen atom include, but are not limited to, fluorine, chlorine, bromine and iodine.

[0178] When R 9 When it is a hydrocarbon group, it is usually a hydrocarbon group containing 1 to 20 carbon atoms, and preferably a hydrocarbon group containing 1 to 10 carbon atoms. 9 Examples include, but are not limited to, straight-chain aliphatic hydrocarbon groups represented by methyl and ethyl, branched aliphatic hydrocarbon groups represented by isopropyl and tert-butyl, alicyclic hydrocarbon groups represented by cyclopentyl and cyclohexyl, and aromatic hydrocarbon groups represented by phenyl. Among them, methyl, ethyl, n-propyl, isopropyl, isobutyl, sec-butyl, tert-butyl, hexyl, cyclopentyl or cyclohexyl are preferably used.

[0179] When R 9 When it is a hydrocarbon group containing heteroatoms, the hydrocarbon group containing heteroatoms is preferably selected from the above-mentioned 8 The examples are those exemplified in the case of the hydrocarbon group containing a heteroatom. Among them, N,N-diethylamino, quinolyl or isoquinolyl is preferred.

[0180] When R 9 In the case of a hydrocarbon group containing a hetero atom, the hydrocarbon group containing a hetero atom may be bonded to Si via any of the carbon atom and the hetero atom constituting the hydrocarbon group containing a hetero atom.

[0181] When the value of f is 2, the two R 9 can be the same or different from each other. Regardless of the value of f, R 9 Can be used with R 8 Same or different.

[0182] In the general formula (5), R 10 Represents a hydrocarbon group. 10 Typically, it is a hydrocarbon group containing 1 to 20 carbon atoms, more preferably a hydrocarbon group containing 1 to 10 carbon atoms, and still more preferably a hydrocarbon group containing 1 to 5 carbon atoms. 10 Examples include, but are not limited to, straight-chain aliphatic hydrocarbon groups represented by methyl and ethyl, and branched aliphatic hydrocarbon groups represented by isopropyl and tert-butyl. Among them, methyl or ethyl is preferred. When the value of g is 2 or more, several R 10 May be the same as or different from each other.

[0183] As organic silicon compounds other than vinylsilane compounds that can be used in the present invention, especially as alkoxysilane compounds, the following are preferred, for example: t-Bu(Me)Si(OMe)2, t-Bu(Me)Si(OEt)2, t-Bu(Et)Si(OMe)2, t-Bu(n-Pr)Si(OMe)2, c-Hex(Me)Si(OMe)2, c-Hex(Et)Si(OMe)2, c-Pen2Si(OMe)2, i-Pr2Si(OMe)2, i-Bu2Si(OMe)2, i-Pr(i-Bu)Si(OMe)2, n-Pr(Me)Si(OMe)2, t-BuSi(OEt)3, (Et2N)2Si(OMe)2, Et2N-Si(OEt)3 and (Et2N)2(c-Pen)Si(OMe).

[0184] In the above examples, Me represents a methyl group; Et represents an ethyl group; t-Bu represents a tert-butyl group; n-Pr represents an n-propyl group; i-Pr represents an isopropyl group; c-Hex represents a cyclohexyl group; and c-Pen represents a cyclopentyl group.

[0185] As the organic silicon compound other than the vinylsilane compound, a single compound may be used, or several compounds may be used in combination.

[0186] The amount of the organosilicon compound other than the vinylsilane compound may be any amount as long as the effect of the present invention is not impaired. The amount of the organosilicon compound is preferably in the range of 0.01 to 1,000, and more preferably in the range of 0.1 to 100, in terms of the molar ratio of the organosilicon compound to titanium (the number of moles of the organosilicon compound / the number of moles of titanium atoms).

[0187] It is believed that the organosilicon compound used in the present invention is as follows: the organosilicon compound coordinates to the vicinity of a titanium atom that can be an active center, such as a Lewis acid site on a magnesium support, and controls catalytic properties such as catalytic activity and polymer regularity. However, this mechanism of action does not limit the technical scope of the present invention.

[0188] (A4: Vinylsilane compound)

[0189] As the vinylsilane compound used in the solid catalyst component of the present invention, it is preferred to use a compound represented by the following general formula (6), which is a compound having the following structure: at least one of the hydrogen atoms of monosilane (SiH4) is substituted by a vinyl group, and a part or all of the remaining hydrogen atoms are substituted by other free radicals.

[0190] [General formula (6)]

[0191] [CH2=CH-] m SiX n R 11 j (OR 12 ) k

[0192] (wherein X represents halogen; R 11 represents a hydrogen atom or a hydrocarbon group; R 12 represents a hydrogen atom, a hydrocarbon group or an organosilicon group; 1≤m≤4; 0≤n≤3; 0≤j≤3; 0≤k≤2; and m+n+j+k=4. )

[0193] In the general formula (6), m represents the number of vinyl groups and is a value of 1 or more and 4 or less. More preferably, the value of m is desired to be 1 or 2, and 2 is particularly preferred.

[0194] In general formula (6), X represents a halogen, such as fluorine, chlorine, bromine and iodine. When there are several halogens, they may be the same or different from each other. Among them, chlorine is particularly preferred. In addition, n represents the number of halogens and is a value of more than 0 and less than 3. More preferably, the value of n is more than 0 and less than 2, and 0 is particularly preferred.

[0195] In the general formula (6), R 11 R represents a hydrogen atom or a hydrocarbon group, and it is preferably a hydrogen atom or a hydrocarbon group containing 1 to 20 carbon atoms, and more preferably a hydrogen atom or a hydrocarbon group containing 1 to 12 carbon atoms. 11 Preferred examples of R include, but are not limited to, a hydrogen atom, an alkyl group represented by a methyl group and a butyl group, a cycloalkyl group represented by a cyclohexyl group, and an aryl group represented by a phenyl group. 11Particularly preferred examples of include, but are not limited to, hydrogen atom, methyl group, ethyl group and phenyl group. In the general formula (6), j represents R 11 The value of j is more preferably 1 or more and 3 or less, still more preferably 2 or more and 3 or less, and particularly preferably 2. When j is 2 or more, R 11 May be the same as or different from each other.

[0196] In the general formula (6), R 12 represents a hydrogen atom, a hydrocarbon group or an organosilicon group. 12 When it is a hydrocarbon group, it can be selected from 11 The same instance group. When R 12 When it is an organosilicon group, it is preferably an organosilicon group including a hydrocarbon group containing 1 to 20 carbon atoms. 12 Examples of the organic silicon group include, but are not limited to, an alkyl group-containing silicon group represented by a trimethylsilyl group, an aryl group-containing silicon group represented by a dimethylphenylsilyl group, a vinyl group-containing silicon group represented by a dimethylvinylsilyl group, and silicon groups formed by combining them, such as a propylphenylvinylsilyl group.

[0197] In addition, k represents R 12 The number of and is a value of 0 or more and 2 or less. In the case of a compound whose value of k is equivalent to 3 (such as vinyltriethoxysilane), the compound does not exhibit the performance of the vinylsilane compound of the present invention, and it exhibits the performance of the alkoxysilane compound of (A3) of the present invention. Therefore, the compound is not suitable for use as a vinylsilane compound. It is believed that the reason is that the compound acts in the same way as tert-butyltriethoxysilane, which is structurally close to the compound (tert-butyltriethoxysilane is effective as the organosilicon compound of (A3) of the present invention). The value of k is more preferably 0 or more and 1 or less, and particularly preferably 0. When the value of k is 2, the two R 12 can be the same or different from each other. Regardless of the value of k, R 11 and R 12 May be the same as or different from each other.

[0198] These vinylsilane compounds may be used alone or in combination.

[0199] Preferred examples of vinyl silane compounds include, but are not limited to, CH2=CH-SiMe3, [CH2=CH-]2SiMe2, CH2=CH-Si(Cl)Me2, CH2=CH-Si(Cl)2Me, CH2=CH-SiCl3, [CH2=CH-]2Si(Cl)Me, [CH2=CH-]2SiCl2, CH2=CH-Si(Ph)Me2, CH2=CH-Si(Ph)2Me, CH2=CH-SiPh3, [CH2=CH-]2Si(Ph)Me, [CH2=CH-]2SiPh2, CH2=CH-Si(H)Me2, CH2=CH-Si(H)2Me, CH2=CH-SiH3, [CH2=CH-]2Si(H)Me, [CH2=CH-]2SiH2, CH2=CH-SiEt3, CH2=CH-SiBu3, CH2=CH-Si(Ph)(H)Me, CH2=CH-Si(Cl)(H)Me, CH2=CH-Si(Me)2(OMe), CH2=CH-Si(Me)2(OSiMe3) and CH2CH-Si(Me)2-OSi(Me)2-CH=CH2. Among them, divinylsilane compounds having m=2 are preferred, and divinyldimethylsilane ([CH2=CH-]2SiMe2) is particularly preferred.

[0200] In the above examples, Ph represents a phenyl group, and other symbols such as Me, Et and Bu are as described above.

[0201] The amount of the vinyl silane compound used can be any amount as long as the effect of the present invention is not impaired. The amount of the vinyl silane compound used is, for example, in the range of 0 to 1000, preferably in the range of 0.001 to 1000, and particularly preferably in the range of 0.01 to 100, based on the molar ratio of the vinyl silane compound to titanium (the number of moles of the vinyl silane compound / the number of moles of titanium atoms).

[0202] The vinylsilane compound used in the present invention is considered as follows: the charge density of the carbon-carbon double bond portion is very high, and the coordination with the titanium atom as the active center is very fast; therefore, the vinylsilane compound is effective in preventing the excessive reduction of the titanium atom caused by the organic aluminum compound and preventing the deactivation of the active site caused by impurities, etc. However, this mechanism of action does not limit the technical scope of the present invention.

[0203] (Method for preparing solid catalyst component)

[0204] The solid catalyst component used in the present invention is obtained by contacting the solid catalyst component with the above-mentioned respective components and forming a solid component.

[0205] The contact conditions of the components need to be free of oxygen. However, any conditions may be adopted as long as the effects of the present invention are not impaired. Generally, the following conditions are preferred.

[0206] The contact temperature is about -50°C to about 200°C, and it is preferably 0°C to 150°C.

[0207] As the contact method, examples include, but are not limited to, a mechanical method using a rotary ball mill or a vibration mill and a contact method by stirring in the presence of an inert diluent.

[0208] In the preparation of the solid catalyst component, washing with an inert solvent may be carried out intermediately and / or finally.

[0209] The inert solvent is preferably, for example, an aliphatic hydrocarbon compound such as heptane, an aromatic hydrocarbon compound such as toluene and xylene, or a halogen-containing hydrocarbon compound such as 1,2-dichloroethylene and chlorobenzene.

[0210] As a method for preparing the solid catalyst component, any method may be used. Examples of the method include, but are not limited to, the following methods (i) to (viii).

[0211] (i) Co-crushing method

[0212] The co-pulverization method is a method of supporting a titanium compound on a magnesium compound by co-pulverizing a magnesium compound containing a halogen (typified by magnesium chloride) and a titanium compound. In this method, the electron-donating compound may be co-pulverized simultaneously or in different steps.

[0213] In addition, a dry pulverization method without using a solvent or a wet pulverization method of co-pulverization in the coexistence of an inert solvent, etc. can be used. For the pulverization, any pulverizer such as a rotary ball mill and a vibration mill can be used.

[0214] (ii) Heat treatment method

[0215] The heat treatment method is a method of supporting a titanium compound on a halogen-containing magnesium compound (represented by magnesium chloride) by stirring and heating the titanium compound and a halogen-containing magnesium compound (represented by magnesium chloride) in an inert solvent so that they are in contact with each other. In this method, an electron-donating compound can be brought into contact with them simultaneously or in different steps.

[0216] When a liquid compound such as titanium tetrachloride is used as the titanium compound, they may be brought into contact with each other in the absence of an inert solvent.

[0217] As required, optional components such as a silicon halide compound may be brought into contact with them simultaneously or in different steps.

[0218] The contact temperature is not particularly limited. In many cases, it is preferred to bring them into contact with each other at a relatively high temperature of about 90°C to about 130°C.

[0219] (iii) Dissolution precipitation method

[0220] The dissolution precipitation method is a method of forming particles by dissolving a halogen-containing magnesium compound (typified by magnesium chloride) by contacting it with an electron-donating compound, and then causing a precipitation reaction by contacting the thus produced solution with a precipitant.

[0221] Among the above-mentioned electron donating compounds, those which can be used for dissolution are, for example, alcohols and ethers.

[0222] As the precipitating agent, examples include, but are not limited to, titanium halogenide compounds, silicon halogenide compounds, hydrogen chloride, hydrocarbon compounds containing halogen, siloxane compounds (including polysiloxane compounds) containing Si-H bonds, and aluminum compounds.

[0223] In order to bring the thus-produced solution and the precipitant into contact with each other, the precipitant may be added to the thus-produced solution, or the thus-produced solution may be added to the precipitant.

[0224] When the titanium compound is not used in both the dissolution step and the precipitation step, the particles formed by the precipitation reaction are further brought into contact with the titanium compound, thereby causing the titanium compound to be supported on the magnesium compound.

[0225] Furthermore, the particles formed by the above method may be contacted with optional components such as a titanium halide compound and a silicon halide compound, or may be contacted with an electron donating compound as required. In this case, the electron donating compound may be different from or the same as the electron donating compound used for dissolution.

[0226] These optional components may be brought into contact in any order without particular limitation. They may be brought into contact with each other in separate steps, or they may be brought into contact with each other during dissolution, during precipitation, during contact with titanium compounds, and the like.

[0227] Furthermore, an inert solvent may be present in all of the dissolving step, the precipitation step, and the step of contacting with the optional components.

[0228] (iv) Granulation method

[0229] The granulation method is a granulation method in which a halogen-containing magnesium compound (represented by magnesium chloride) is dissolved by contacting the halogen-containing magnesium compound (represented by magnesium chloride) with an electron-donating compound as in the dissolution precipitation method, and then the solution thus produced is granulated mainly by a physical method. Examples of the electron-donating compound used for dissolution are the same as those provided in the dissolution precipitation method.

[0230] As the granulation method, examples include, but are not limited to, a method of adding a high-temperature solution dropwise to a low-temperature inert solvent, a method of spraying a solution from a nozzle into a high-temperature gas phase and drying the sprayed solution, and a method of spraying a solution from a nozzle into a low-temperature gas phase and cooling the sprayed solution.

[0231] The particles formed by the granulation are brought into contact with a titanium compound, whereby the titanium compound is supported on the magnesium compound.

[0232] Furthermore, the particles may be contacted with an optional component such as a silicon halide compound and an electron donating compound as required. In this case, the electron donating compound may be different from or the same as the electron donating compound used for dissolution.

[0233] These optional components may be brought into contact in any order without particular limitation. They may be brought into contact with each other in separate steps, or they may be brought into contact with each other during dissolution or during contact with the titanium compound.

[0234] Furthermore, an inert solvent may be present in all of the dissolving step, the contacting step with the titanium compound, and the contacting step with the optional components.

[0235] (v) Magnesium (Mg) compound halogenation method

[0236] The magnesium (Mg) compound halogenation method is a method of halogenating a halogen-free magnesium compound by bringing the halogen-free magnesium compound into contact with a halogenating agent. In this method, the electron-donating compound may be brought into contact with them simultaneously or in different steps.

[0237] As the halogen-free magnesium compound, examples include, but are not limited to, dialkoxymagnesium compounds, magnesium oxide, magnesium carbonate, and magnesium salts of fatty acids.

[0238] When a dialkoxymagnesium compound is used, a dialkoxymagnesium compound prepared by reacting metal magnesium with an alcohol in situ can be used. When this preparation method is used, generally, particle formation is performed by granulation or the like at the stage of a halogen-free magnesium compound (starting material).

[0239] As the halogenating agent, examples include, but are not limited to, titanium halide compounds, silicon halide compounds, and phosphorus halide compounds.

[0240] When a halogenated titanium compound is not used as the halogenating agent, the magnesium compound containing halogen formed by halogenation is further brought into contact with a titanium compound, whereby the titanium compound is supported on the magnesium compound.

[0241] Furthermore, the particles formed by the above-described method may be brought into contact with an optional component such as a titanium halide compound and a silicon halide compound, or they may be brought into contact with an electron donating compound, as required.

[0242] These optional components may be contacted in any order without particular limitation. They may be contacted with each other in separate steps, or they may be contacted with each other during the halogenation of the halogen-free magnesium compound or during the contact with the titanium compound.

[0243] Furthermore, an inert solvent may be present in both the step of contacting with the titanium halide compound and the step of contacting with the optional components.

[0244] (vi) Precipitation method from organomagnesium compound

[0245] The method of precipitation from an organomagnesium compound is a method of contacting a precipitant with a solution of an organomagnesium compound such as a Grignard reagent (typified by butylmagnesium chloride) and a dialkylmagnesium compound. In this method, an electron donating compound may be contacted with them simultaneously or in different steps.

[0246] As the precipitating agent, examples include, but are not limited to, titanium compounds, silicon compounds and hydrogen chloride.

[0247] When the titanium compound is not used as the precipitating agent, the particles formed by the precipitation reaction are further brought into contact with a titanium compound, whereby the titanium compound is supported on the magnesium compound.

[0248] Furthermore, the particles formed by the above-described method may be brought into contact with an optional component such as a titanium halide compound and a silicon halide compound, or they may be brought into contact with an electron donating compound, as required.

[0249] These optional components may be brought into contact in any order without particular limitation. They may be brought into contact with each other in separate steps, or they may be brought into contact with each other during precipitation or during contact with the titanium compound.

[0250] Furthermore, an inert solvent may be present in all of the precipitation step, the contacting step with the titanium compound, and the contacting step with the optional components.

[0251] (vii) Immersion method

[0252] The impregnation method is a method of impregnating a support composed of an inorganic compound or a support composed of an organic compound with a solution of an organic magnesium compound or a solution obtained by dissolving a magnesium compound in an electron donating compound.

[0253] Examples of the organomagnesium compound are the same as those in the above-mentioned method of precipitation from the organomagnesium compound. The magnesium compound used to dissolve the magnesium compound may contain halogen or may not contain halogen. Examples of the electron-donating compound are the same as those in the above-mentioned dissolution precipitation method.

[0254] As the support composed of an inorganic compound, examples include, but are not limited to, silica, alumina, and magnesia.

[0255] As the carrier composed of an organic compound, examples include, but are not limited to, polyethylene, polypropylene, and polystyrene.

[0256] On the support particles after the impregnation treatment, the magnesium compound is precipitated and fixed by a chemical reaction with a precipitant or by a physical treatment such as drying.

[0257] Examples of the precipitant are the same as those in the above-mentioned dissolution precipitation method.

[0258] When the titanium compound is not used as a precipitant, the particles formed in this manner are further contacted with a titanium compound, thereby supporting the titanium compound on the magnesium compound. In addition, as required, the particles formed in this manner may be contacted with optional components such as a titanium halide compound and a silicon halide compound, or may be contacted with an electron donating compound.

[0259] These optional components may be contacted in any order without particular limitation. They may be contacted with each other in separate steps, or they may be contacted with each other during impregnation, during precipitation, during drying, or during contact with the titanium compound. In addition, an inert solvent may be present in all of the impregnation step, the precipitation step, the step of contacting with the titanium compound, and the step of contacting with the optional components.

[0260] (viii) Composite method

[0261] The above methods (i) to (vii) can be used in combination. As a combination of methods, examples include, but are not limited to, the following: "a method of co-crushing magnesium chloride and an electron-donating compound, and then heating and treating with a titanium halide compound", "a method of co-crushing magnesium chloride and an electron-donating compound, and then dissolving with another electron-donating compound, and then precipitating with a precipitant", "a method of dissolving a dialkoxymagnesium compound by an electron-donating compound, precipitating them by contacting with a titanium halide compound, and halogenating the magnesium compound at the same time", and "a method of contacting a dialkoxymagnesium compound with carbon dioxide, forming a carbonate magnesium compound and dissolving it at the same time, impregnating silica with the solution produced, and contacting the impregnated silica with hydrogen chloride, thereby halogenating the magnesium compound and simultaneously precipitating and fixing the magnesium halide compound, and then contacting the precipitated and fixed magnesium halide compound with a titanium halide compound, thereby supporting the titanium compound".

[0262] When the solid catalyst component is a solid catalyst component obtained by further contacting the solid component (A1) with an organoaluminum compound (A2), an organosilicon compound (A3) other than a vinylsilane compound, and a vinylsilane compound (A4) etc. after forming the solid component (A1), the method for contacting the components with each other is not particularly limited. Generally, the components can be contacted with each other while stirring the above components in the presence of an inert solvent.

[0263] As the inert solvent, examples include, but are not limited to, liquid saturated hydrocarbons such as hexane, heptane, octane, decane, dodecane and liquid paraffin and silicone oil having a structure of dimethylpolysiloxane. These inert solvents can be used alone, or they can be used in combination of two or more as a mixed solvent. The inert solvent is preferably used after impurities such as oxygen, water and sulfur compounds that have a negative impact on the polymerization are removed therefrom.

[0264] The contact conditions may be any conditions as long as the effects of the present invention are not impaired. The contact temperature is generally about -50°C to about 200°C, preferably -10°C to 100°C, more preferably 0°C to 70°C, and still more preferably 10°C to 60°C.

[0265] When the solid catalyst component is a solid catalyst component obtained by further contacting the solid component (A1) with an organoaluminum compound (A2) and an organosilicon compound (A3) other than a vinylsilane compound after forming the solid component (A1), any process can be used as the contact process of the solid component (A1) with the organoaluminum compound (A2) and the organosilicon compound (A3) other than a vinylsilane compound. As the process, examples include, but are not limited to, the following processes (i) to (iv). Among them, processes (i) and (ii) are preferred.

[0266] Step (i): A method of contacting the solid component (A1) with an organosilicon compound (A3) other than a vinylsilane compound and then contacting it with an organoaluminum compound (A2).

[0267] Step (ii): A method of contacting the solid component (A1) with an organoaluminum compound (A2) and then contacting with an organosilicon compound (A3) other than a vinylsilane compound.

[0268] Step (iii): A method of bringing an organosilicon compound (A3) other than a vinylsilane compound into contact with an organoaluminum compound (A2) and then bringing the organic silicon compound (A3) into contact with the solid component (A1).

[0269] Step (iv): A method of bringing all components into contact with each other simultaneously.

[0270] The number of times the solid component (A1), the organoaluminum compound (A2) and the organosilicon compound (A3) other than the vinylsilane compound are brought into contact with each other may be any number. In this case, the components used several times may be the same as or different from each other.

[0271] The preferred range of the amount of each component is as described above. This is the amount of each component used for each contact. If the components are contacted several times, they can be contacted any number of times as long as the amount of each contact component falls within the range of the above amount.

[0272] When the solid catalyst component is brought into contact with other components, any contact method, any contact conditions and any contact procedure may be adopted.

[0273] When the solid catalyst component is a solid catalyst component obtained by further contacting the solid component (A1) with an organoaluminum compound (A2), an organosilicon compound (A3) other than a vinylsilane compound, and a vinylsilane compound (A4) after forming the solid component (A1), any process can be used as the contact process of the solid component (A1) with the organoaluminum compound (A2), the organosilicon compound (A3) other than a vinylsilane compound, and the vinylsilane compound (A4). As the process, examples include, but are not limited to, the following processes (iv) to (vii). Among them, processes (iv) and (v) are preferred.

[0274] Step (iv): A method of contacting the solid component (A1) with a vinylsilane compound (A4), with an organosilicon compound (A3) other than the vinylsilane compound, and then with an organoaluminum compound (A2).

[0275] Step (v): A method of bringing an organosilicon compound (A3) other than a vinylsilane compound into contact with a vinylsilane compound (A4), bringing it into contact with a solid component (A1), and then bringing it into contact with an organoaluminum compound (A2).

[0276] Step (vi): A method of contacting the solid component (A1) with a vinylsilane compound (A4), and then contacting with an organosilicon compound (A3) other than the vinylsilane compound and an organoaluminum compound (A2).

[0277] Step (vii): A method of bringing all components into contact with each other simultaneously.

[0278] The solid component (A1), the organoaluminum compound (A2), the organosilicon compound (A3) other than the vinylsilane compound, and the vinylsilane compound (A4) may be contacted with each other any number of times. In this case, the components used several times may be the same or different from each other.

[0279] The preferred range of the amount of each component is as described above. This is the amount of each component used for each contact. If the components are contacted several times, they can be contacted any number of times as long as the amount of each contact component falls within the range of the above amount.

[0280] When the solid catalyst component is brought into contact with other components, any contact method, any contact conditions and any contact procedure may be adopted.

[0281] (Prepolymerization of Solid Catalyst Component)

[0282] Solid catalyst component prepolymerization can be made. In the presence of solid catalyst component, the compound comprising olefinic double bonds is polymerized in a small amount under mild conditions as monomer (prepolymerized monomer). Therefore, a part or all of the prepolymerized monomers are polymerized into a polymer (prepolymerized polymer) of a compound comprising olefinic double bonds, which can be used as a solid catalyst component suitable for the polymerization of propylene-based block copolymers.

[0283] As prepolymer monomers, examples include, but are not limited to, olefins represented by ethylene, propylene, 1-butene, 3-methylbutene-1, 4-methylpentene-1, 1-pentene, 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-eicosene, 4-methyl-1-pentene and 3-methyl-1-pentene; styrene analogs represented by styrene, α-methylstyrene, allylbenzene and chlorostyrene; and diene compounds represented by 1,3-butadiene, isoprene, 1,3-pentadiene, 1,5-hexadiene, 2,6-octadiene, dicyclopentadiene, 1,3-cyclohexadiene, 1,9-decadiene and divinylbenzene. Among them, ethylene, propylene, 3-methylbutene-1, 4-methylpentene-1, styrene and divinylbenzene are preferred. They can be used alone or in combination of two or more.

[0284] In order to adjust the molecular weight of the polymer produced by the prepolymerization, a molecular weight regulator such as hydrogen may be used in combination.

[0285] The solid catalyst component obtained by prepolymerization comprises a polymer (prepolymerized polymer) of a compound comprising an olefinic double bond. When propylene homopolymerization or copolymerization is made by using a solid catalyst component, the prepolymerized polymer plays the role of a shell. Therefore, the effect of suppressing the fine powder produced by the catalyst particles caused by crushing in the main polymerization is obtained.

[0286] From the viewpoint of producing a sufficient amount of the prepolymerized polymer in the prepolymerization process, the amount of the prepolymerized monomer used is preferably 0.1 part by mass or more, more preferably 0.2 part by mass or more, still more preferably 0.4 part by mass or more, and even more preferably 0.5 part by mass or more relative to 1 part by mass of the solid catalyst component before the prepolymerization.

[0287] The upper limit of the amount of prepolymerized monomer used is not particularly limited. From the viewpoint of preventing the amount of prepolymerized polymer generated from excessively increasing, the amount of prepolymerized monomer relative to 1 part by mass of the solid catalyst component before prepolymerization is preferably 20 parts by mass or less, more preferably 15 parts by mass or less, and still more preferably 10 parts by mass or less.

[0288] The amount of the prepolymerized polymer contained in the solid catalyst component after prepolymerization, that is, the prepolymerization amount is preferably 0.1 parts by mass or more, more preferably 0.2 parts by mass or more, still more preferably 0.4 parts by mass or more, and even more preferably 0.5 parts by mass or more relative to 1 part by mass of the solid catalyst component before prepolymerization. When the prepolymerization amount is within the above range, the effect of suppressing the generation of fine powder due to broken catalyst particles is obtained.

[0289] The upper limit of the prepolymerization amount is not particularly limited. From the viewpoint of productivity and economy, the upper limit of the prepolymerization amount is preferably 20 mass parts or less relative to the solid catalyst component before 1 mass part prepolymerization, more preferably 15 mass parts or less, and even more preferably 10 mass parts or less. This is because, even if the prepolymerization amount is increased to be higher than this scope, the catalyst performance also reaches a peak value.

[0290] The prepolymerization method is not particularly limited. Usually, the prepolymerization is carried out while stirring the components in the presence of an inert solvent. As an inert solvent, examples include, but are not limited to, liquid saturated hydrocarbons such as hexane, heptane, octane, decane, dodecane and liquid paraffin and silicone oils with the structure of dimethylpolysiloxane. These inert solvents can be used alone, or they can be used as a mixed solvent in a combination of two or more. The inert solvent is preferably used after impurities such as oxygen, water and sulfur compounds that have a negative impact on the polymerization are removed therefrom.

[0291] The prepolymerization conditions may be any conditions as long as the effects of the present invention are not impaired.

[0292] The prepolymerization reaction temperature is usually about -50°C to about 200°C, preferably -10°C to 100°C, and more preferably 0°C to 70°C.

[0293] The preliminary polymerization may be carried out in the presence of an organoaluminum compound. As the organoaluminum compound, examples include, but are not limited to, those exemplified above as the organoaluminum compound (A2).

[0294] The amount of the organoaluminum compound used in the prepolymerization step is in the range of 0.1 mol to 40 mol, and preferably in the range of 0.3 mol to 20 mol, relative to 1 mol of the titanium atom of the solid catalyst component.

[0295] In addition, the prepolymerization can be carried out in the presence of an alkoxysilane compound. As the alkoxysilane compound, examples include, but are not limited to, those exemplified as the organosilicon compound (A3) other than the vinylsilane compound. The amount of the alkoxysilane compound used in the prepolymerization step is preferably in the range of 0.01 mol to 10 mol relative to 1 mol of titanium contained in the solid catalyst component.

[0296] Prepolymerization can be carried out in batches. The prepolymerized monomers used in this case can be the same or different from each other. In addition, washing with inert solvents such as hexane and heptane can be carried out after prepolymerization. After prepolymerization is completed, according to the use form of the catalyst, the catalyst can continue to be used as it is, or it can be dried.

[0297] In addition, as long as the effect of the present invention is not impaired, the optional component can be added during the washing or drying after the prepolymerization, or it can be added after washing or drying. As the optional component, examples include, but are not limited to, polymers such as polyethylene, polypropylene and polystyrene and inorganic oxide solids such as silicon dioxide and titanium dioxide.

[0298] 2. Component (B): Organic aluminum compound

[0299] In the present invention, as the organoaluminum compound (B) which can be used in the catalyst for olefin polymerization during the main polymerization, examples include, but are not limited to, the compounds disclosed in JP-A No. 2004-124090. The organoaluminum compound (B) can be preferably selected from the same group as the examples of the organoaluminum compound (A2) provided above as a component for preparing the solid catalyst component (A).

[0300] The organoaluminum compound (B) may be the same as or different from the organoaluminum compound (A2) used in the preparation of the solid catalyst component (A).

[0301] As the organoaluminum compound (B), one compound or a combination of two or more compounds can be used.

[0302] The amount of the organoaluminum compound (B) used is preferably in the range of 1 to 5,000, and particularly preferably in the range of 10 to 500, in terms of the molar ratio to the titanium component constituting the solid catalyst component (A) (i.e., the number of moles of the organoaluminum compound / the number of moles of titanium atoms in the solid catalyst component).

[0303] 3. Electron donating compounds used as external donors

[0304] In the present invention, the catalyst for olefin polymerization may include, in its constituent components, an electron donating compound serving as an external donor.

[0305] In the polymerization technology using Ziegler catalysts, as described above, the external donor changes the properties of the active sites that have been formed. For example, by further using the external donor in the prepared solid catalyst component, the active sites that have been formed can be changed to highly stereospecific active sites, and the active sites that can produce non-crystalline components can be poisoned. Therefore, a propylene-based polymer with higher stereoregularity and less content of non-crystalline components can be produced.

[0306] Examples of the electron donating compound (external donor) include, but are not limited to, an organosilicon compound (C), a compound containing at least two ether bonds (D), a compound containing a C(=O)N bond in the molecule (E), and a sulfite compound (F). As the electron donating compound, one compound or a combination of two or more compounds may be used.

[0307] (Organosilicon compound (C))

[0308] As the organosilicon compound (C), compounds disclosed in JP-A No. 2004-124090 can be used. The organosilicon compound (C) can be preferably selected from the same group as exemplified by the organosilicon compound (A3) used for preparing the solid catalyst component (A).

[0309] The organosilicon compound (C) may be the same as or different from the organosilicon compound (A3) other than the vinylsilane compound used in the preparation of the solid catalyst component (A).

[0310] As the organosilicon compound (C), one compound or a combination of two or more compounds can be used.

[0311] (Compound (D) containing at least two ether bonds)

[0312] As the compound (D) containing at least two ether bonds, for example, compounds disclosed in JP-A Nos. H03-294302 and H08-333413 can be used. In general, it is desirable to use a compound represented by the following formula.

[0313] [General formula (7)]

[0314] R 15 OC(R 14 )2-C(R 13 )2-C(R 14 )2-OR 15

[0315] (where R 13 and R 14 Each represents a hydrogen atom, a hydrocarbon group or an optional radical selected from hydrocarbon groups containing a heteroatom, and R 15 represents a hydrocarbon group or a hydrocarbon group containing a heteroatom. )

[0316] As the compound containing at least two ether bonds, examples include, but are not limited to, 2,2-diisopropyl-1,3-dimethoxypropane, 2,2-diisobutyl-1,3-dimethoxypropane, 2-isobutyl-2-isopropyl-1,3-dimethoxypropane, 2-isopropyl-2-isopentyl-1,3-dimethoxypropane, 2,2-dicyclopentyl-1,3-dimethoxypropane, and 9,9-bis(methoxymethyl)fluorene. As the compound containing at least two ether bonds, a single compound may be used, or several compounds may be used in combination.

[0317] (Compound (E) containing a C(=O)N bond in the molecule)

[0318] As the compound (E) containing a C(═O)N bond in the molecule, for example, compounds disclosed in JP-A No. 2004-124090 can be used. For example, preferred are tetramethylurea, 1,3-dimethyl-2-imidazolidinone, and 1-ethyl-2-pyrrolidone.

[0319] (Sulfite compound (F))

[0320] As the sulfite compound, for example, compounds disclosed in JP-A No. 2006-225449 can be used. For example, dimethyl sulfite and diethyl sulfite are preferred.

[0321] The amount of the electron donating compound (external donor) used is preferably in the range of 0.01 to 10,000, and particularly preferably in the range of 0.5 to 500 in terms of molar ratio to titanium constituting the solid catalyst component (i.e., molar number of the electron donating compound / molar number of titanium atoms in the solid catalyst component).

[0322] III. Propylene polymers produced

[0323] In the propylene polymer produced by the present invention, the melt flow rate (MFR) of the first propylene polymer can be controlled by using a molecular weight regulator such as hydrogen in the polymerization step during the homopolymerization of propylene produced by the first step or during the copolymerization of propylene with other α-olefins. The MFR of the propylene polymer is set according to the molding method or according to the purpose. The MFR value (unit: g / 10min) measured under the measurement conditions of 230°C and a load of 2.16kg is generally 0.1 or more, preferably 0.5 or more, and more preferably 1 or more. On the other hand, it is 500 or less, preferably 400 or less, and more preferably 300 or less. When the MFR is too small, the polymer fluidity is significantly deteriorated and molding is difficult. When the MFR is too large, a decrease in tensile properties occurs.

[0324] In the present invention, the first propylene-based polymer means a copolymer of a propylene homopolymer or propylene and a comonomer. As a comonomer, at least one selected from the group consisting of straight and branched alpha-olefins each containing 2 to 10 carbon atoms except propylene can be used. Usually, ethylene or 1-butene is preferred. The content of the comonomer is preferably in the range of 0 mass % to 10 mass %, more preferably in the range of 0 mass % to 6 mass %, and even more preferably in the range of 0 mass % to 4 mass %. When the comonomer content is outside this range, the amount of the component with too low crystallinity increases, which may cause the block polymer to be easily formed due to melting or fusion during the polymerization reaction.

[0325] In the second step, the intrinsic viscosity [η] of the propylene-based polymer can be controlled by using a molecular weight modifier such as hydrogen in the polymerization step. From the viewpoint of properties such as melt tension increase and flow mark improvement, and from the viewpoint of improving product appearance by suppressing the number of gels, the intrinsic viscosity [η] of the propylene-ethylene copolymer is preferably in the range of 2 dL / g to 12 dL / g, and more preferably in the range of 2.5 dL / g to 10 dL / g.

[0326] In the present invention, the second propylene-based polymer can be a propylene homopolymer or a copolymer with a comonomer. As a comonomer, at least one selected from the group consisting of straight and branched alpha-olefins each containing 2 to 10 carbon atoms except propylene can be used. Usually, ethylene or 1-butene is preferred. The content of the comonomer is preferably in the range of 0 mass % to 90 mass %, more preferably in the range of 0 mass % to 70 mass %, and even more preferably in the range of 0 mass % to 50 mass %. When the comonomer content is outside this range, the compatibility of the first propylene-based polymer and the second propylene-based polymer with each other may be reduced, which may cause the quality of the final product, such as the reduction of impact resistance. In addition, the comonomer content of the first propylene-based polymer and the comonomer content of the second propylene-based polymer may be equal to or different from each other.

[0327] From the viewpoint of finely dispersing the components produced in each polymerization step and maintaining the quality of the final product (e.g., appearance and impact resistance) at a high level, the second propylene-based polymer produced in the second step is preferably a copolymer of propylene and at least one monomer selected from the group consisting of α-olefins having 2 to 10 carbon atoms other than propylene, and the content of at least one monomer selected from the group consisting of α-olefins having 2 to 10 carbon atoms other than propylene is preferably in the range of 20% by mass to 80% by mass, and more preferably in the range of 30% by mass to 70% by mass.

[0328] When all propylene-based polymers are 100 mass%, it is preferred that the first propylene-based polymer is 98 mass% to 40 mass%, and the second propylene-based polymer is 2 mass% to 60 mass%; it is more preferred that the second propylene-based polymer is 3 mass% to 55 mass%, and the first propylene-based polymer is 97 mass% to 45 mass%; and it is still more preferred that the second propylene-based polymer is 3 mass% to 45 mass%, and the first propylene-based polymer is 97 mass% to 55 mass%.

[0329] Example

[0330] Hereinafter, the present invention will be described in more detail with reference to Examples. However, the present invention is not limited to these Examples. The following shows the measurement method of each physical property value in the present invention.

[0331] [Measurement of various physical properties]

[0332] (1)MFR

[0333] The MFR of the propylene-based polymer obtained in each example was evaluated under the conditions in accordance with JIS K7210 (230° C., 2.16 kg load).

[0334] (2) Analysis method of propylene block copolymers

[0335] In the case of producing a so-called propylene-based block copolymer by polymerizing a propylene-ethylene random copolymer having a high comonomer content and not showing a clear melting point in at least one of the first step and the second step, the ratio (Wc) and ethylene content (Gv) of the propylene-based copolymer part and the intrinsic viscosity [η] are measured using the following cross-classification apparatus and conditions.

[0336] When both the comonomer content of the first step and the comonomer content of the second step are small and each polymer or comonomer has a clear melting point, the production amount in each polymerization step is calculated from the flow rate of the refrigerant supplied for removing the polymerization reaction heat in each polymerization step and the temperature difference between the inlet and the outlet. Then, the productivity in the second step is obtained by the following calculation formula: [Production amount in the second step] / ([Production amount in the first step]+[Production amount in the second step])×100.

[0337] (2-1) Analyzer used

[0338] (i) Cross-grading device

[0339] "CFC T-100" manufactured by DIA Instruments Co., Ltd. (hereinafter abbreviated as "CFC")

[0340] (ii) Fourier transform infrared absorption spectroscopy

[0341] FT-IR "1760X" manufactured by Perkin Elmer, Inc.

[0342] Instead of the wavelength fixed type infrared spectrophotometer installed as the detector of CFC, FT-IR was connected. This FT-IR was used as the detector. The transfer line from the outlet of the solution eluted by CFC to the FT-IR was set to 1 m and maintained at 140° C. throughout the measurement. The optical path length of the flow cell installed to the FT-IR was 1 mm and the optical path width was And it was kept at 140°C during the whole measurement period.

[0343] (iii) Gel Permeation Chromatography (GPC):

[0344] As the GPC column in the CFC latter stage part, three "AD806MS" columns manufactured by Showa Denko KK connected in series were used.

[0345] (2-2) CFC measurement conditions

[0346] (i) Solvent: o-dichlorobenzene (ODCB)

[0347] (ii) Sample concentration: 4 mg / mL

[0348] (iii) Injection volume: 0.4 mL

[0349] (iv) Crystallization: The temperature was reduced from 140°C to 40°C in about 40 minutes.

[0350] (v) Grading method:

[0351] The fractionation temperature during temperature-elution fractionation was set at 40°C, 100°C and 140°C and the fractionation was divided into three fractions in total. The elution ratios (unit: mass %) of the component eluted below 40°C (fraction 1), the component eluted at a temperature of 40°C to 100°C (fraction 2) and the component eluted at a temperature of 100°C to 140°C (fraction 3) were defined as W40, W100 and W140, respectively. W40+W100+W140=100. The fractions obtained were automatically transported to the FT-IR analyzer as they were.

[0352] (vi) Solvent flow rate during elution: 1 mL / min

[0353] (2-3) FT-IR measurement conditions

[0354] After starting the elution of the sample solution from the GPC of the CFC rear stage, FT-IR measurement was performed under the following conditions, and GPC-IR data on each of the above-mentioned fractions 1 to 3 were collected.

[0355] (i) Detector: MCT

[0356] (ii) Resolution: 8cm -1

[0357] (iii) Measurement interval: 0.2 minutes (12 seconds)

[0358] (vi) Cumulative number of measurements per time: 15 times

[0359] (2-4) Post-processing and analysis of measurement results

[0360] The elution amount and molecular weight distribution of the components eluted at each temperature were calculated using the FT-IR spectra at 2945 cm-1 The absorbance at 1000 nm was determined as the chromatogram. The elution volume was standardized so that the sum of the elution volumes of the eluted components was 100%. The conversion from retention volume to molecular weight was performed using a calibration curve prepared in advance using standard polystyrene.

[0361] The standard polystyrenes used are products manufactured by Tosoh Corporation with the following trade names: F380, F288, F128, F80, F40, F20, F10, F4, F1, A5000, A2500, and A1000.

[0362] The calibration curve was prepared by injecting 0.4 mL of a solution prepared by dissolving each standard polystyrene in ODCB to obtain a concentration of 0.5 mg / mL (containing 0.5 mg / mL of BHT). As the calibration curve, a cubic expression obtained by least squares approximation was used. For the conversion to molecular weight, a universal calibration curve was used with reference to Sadao Mori, "Size Exclusion Chromatography", (Kyoritsu Shuppan Co., Ltd.). For the viscosity expression ([η] = K × Mα) used in this article, the following values ​​were used.

[0363] (i) When the calibration curve is prepared using standard polystyrene: K = 0.000138, α = 0.70

[0364] (ii) When measuring a sample of a propylene-based block copolymer: K = 0.000103, α = 0.78

[0365] The ethylene content distribution of each eluted component (the distribution of ethylene content along the molecular weight axis) was determined by using polyethylene, polypropylene, and ethylene content of each component preliminarily. 13 The calibration curve prepared by C-NMR measurement of known ethylene-propylene rubber (EPR) or its mixture will be at 2956 cm -1 The absorbance at 2927 cm -1 The ethylene content was determined by converting the absorbance at 400 nm to that at 400 nm (both obtained by FT-IR) to determine the ethylene content (mass %).

[0366] (2-5) Ratio of propylene-ethylene random copolymer part (Wc)

[0367] The ratio (Wc) of the propylene-ethylene random copolymer portion in the propylene-based block copolymer of the present invention is theoretically defined by the following formula (I) and is determined by the following procedure.

[0368] Wc (mass %) = W 40 ×A 40 / B 40+W 100 ×A 100 / B 100 (I)

[0369] In formula (I), W 40 and W 100 Each represents the elution ratio of the above-mentioned fractions (unit: mass %); A 40 and A 100 Each of them corresponds to W 40 and W 100 The average ethylene content (unit: mass %) measured at each fraction of B 40 and B 100 Each represents the ethylene content (unit: mass %) of the propylene-ethylene random copolymer part contained in each fraction. 40 , A 100 , B 40 and B 100 This will be determined in the manner described below.

[0370] The meaning of formula (I) is as follows. Specifically, the first term on the right side of formula (I) is a term for calculating the amount of the propylene-ethylene random copolymer portion contained in fraction 1 (the portion soluble at 40°C). When fraction 1 does not contain a crystalline propylene-based polymer portion and contains only a propylene-ethylene random copolymer, W40 directly contributes to the content of the propylene-ethylene random copolymer portion derived from fraction 1 as a whole. However, in addition to the components derived from the propylene-ethylene random copolymer, fraction 1 also contains a small amount of components derived from the crystalline propylene-based polymer portion (components with extremely low molecular weight and random polypropylene). Therefore, it is necessary to consider the correction of the crystalline propylene-based polymer portion. Therefore, by converting W 40 Multiply by A 40 / B 40 , calculate the amount of the component derived from the propylene-ethylene random copolymer part in fraction 1. For example, the average ethylene content (A) in fraction 1 40 ) is 30% by mass and the ethylene content of the propylene-ethylene random copolymer contained in fraction 1 (B 40 ) is 40 mass %, 30 / 40 = 3 / 4 (i.e., 75 mass %) of fraction 1 is derived from the propylene-ethylene random copolymer, and 1 / 4 is derived from the crystalline propylene-based polymer portion. 40 / B 40 The operation of means to calculate the mass % (W) of the propylene-ethylene random copolymer to fraction 1 40 ). This also applies to the second term on the right. The contribution of the propylene-ethylene random copolymer is calculated for each fraction and summed, thus obtaining the content of the propylene-ethylene random copolymer part.

[0371] (i) As described above, the average ethylene contents corresponding to fractions 1 and 2 obtained by CFC measurement are respectively given by A 40 and A 100 The average ethylene content is expressed as (each unit is mass %).

[0372] (ii) The ethylene content corresponding to the peak position in the differential molecular weight distribution curve of fraction 1 is defined as B40 (unit: mass %). With respect to fraction 2, since it is considered that all the propylene-ethylene random copolymer parts elute at 40°C, the same definition cannot be used. Therefore, in the present invention, the ethylene content is substantially defined as B40. 100 =100. Although B 40 and B 100 Each represents the ethylene content of the propylene-ethylene random copolymer part contained in each fraction, but it is impossible to determine the value by analysis in practice. This is because there is no means to completely separate and recover the propylene homopolymer and the propylene-ethylene random copolymer present as a mixture in the fraction. As a result of studies using various model samples, it was found that when the ethylene content corresponding to the peak position of the differential molecular weight distribution curve of fraction 1 is used as B 40 When B 100 The B value of approximately 100 is judged based on the fact that the amount of the propylene-ethylene random copolymer contained in these fractions is relatively small compared to the amount of the propylene-ethylene random copolymer part contained in fraction 1 because of the crystallinity derived from the ethylene chain and the fact that the amount of the propylene-ethylene random copolymer part contained in these fractions is relatively small compared to the amount of the propylene-ethylene random copolymer part contained in fraction 1. 100 It matches the actual state very well and hardly causes errors in calculation. 100 =100 for the analysis.

[0373] (iii) Due to the above reasons, the ratio (Wc) of the propylene-ethylene random copolymer portion is determined according to the following formula.

[0374] Wc (mass %) = W 40 ×A 40 / B 40 +W 100 ×A 100 / 100 (II)

[0375] Specifically, (W) as the first term on the right side of formula (II) 40 ×A 40 / B 40 ) represents the content (mass %) of the propylene-ethylene random copolymer having no crystallinity, and as the second item (W 100 ×A 100 / 100) represents the content (mass %) of the propylene-ethylene random copolymer portion having crystallinity.

[0376] As used herein, B 40 and the average ethylene content A of fractions 1 and 2 obtained by CFC measurement 40 and A 100 It is determined as follows.

[0377] The ethylene content corresponding to the peak position of the differential molecular weight distribution curve is B 40 In addition, the sum of the products of the mass ratio at each data point and the ethylene content at each data point becomes the average ethylene content A of fraction 1. 40 , each data point is obtained as a data point during measurement. Average ethylene content A of fraction 2 100 Determined in the same way.

[0378] The significance of setting three different fractionation temperatures is as follows. In the CFC analysis of the present invention, 40°C is a necessary and sufficient temperature condition for fractionating only polymers that do not have crystallinity (e.g., most of the propylene-ethylene random copolymer, or components with extremely low molecular weight and random components in the crystalline propylene-based polymer portion); 100°C is a necessary and sufficient temperature for eluting only components that are insoluble at 40°C but soluble at 100°C (e.g., components in the propylene-ethylene random copolymer that have crystallinity due to ethylene and / or propylene chains, and crystalline propylene-based polymer portions); and 140°C is a necessary and sufficient temperature for eluting only components that are insoluble at 100°C but soluble at 140°C (e.g., components with particularly high crystallinity in the crystalline propylene-based polymer portion and components with extremely high molecular weight and extremely high ethylene crystallinity in the propylene-ethylene random copolymer) and recovering the entire amount of propylene-based block copolymers provided for analysis. Due to W 140 Since the propylene-ethylene random copolymer component is not contained at all or, even if contained, is contained in a substantially negligible amount, W is excluded from the calculation of the ratio of the propylene-ethylene random copolymer or the ethylene content of the propylene-ethylene random copolymer. 140 .

[0379] (2-6) Ethylene content of propylene-ethylene random copolymer (Gv)

[0380] The ethylene content of the propylene-ethylene random copolymer portion in the propylene-based block copolymer of the present invention can be determined according to the following formula using the values ​​described above.

[0381] Ethylene content of propylene-ethylene random copolymer (mass %) = (W 40 ×A 40 +W 100 ×A 100 ) / Wc

[0382] In the formula, Wc represents the ratio (mass %) of the propylene-ethylene random copolymer portion determined previously.

[0383] (2-7) Measurement of intrinsic viscosity

[0384] The intrinsic viscosity [η]p of the crystalline propylene-based polymer portion and the propylene-ethylene random copolymer portion in the propylene-based block copolymer of the present invention is measured by an Ubbelohde viscometer at a temperature of 135°C while using decalin as a solvent.

[0385] After the polymerization of the crystalline propylene polymer part is completed, the intrinsic viscosity [η]p of a portion of the polymer sampled from the polymerization reactor is measured. Next, the intrinsic viscosity [η]F of the final polymer (F) obtained by the polymerization of the crystalline propylene polymer part and then the polymerization of the propylene-ethylene random copolymer is measured. [η]c is determined by the following relationship.

[0386] [η]F=(100-Wc) / 100×[η]p+Wc / 100×[η]c

[0387] (3) Evaluation method of aggregated bulk polymers

[0388] As an indicator of the stability of continuous production in the present invention, the aggregated block polymer is evaluated by the following method. In particular, the final product is passed through a 5.5 mesh sieve. When more than 3% by mass (the total amount of the polymer used for evaluation is considered to be 100% by mass) of the polymer remains on the sieve, the result is evaluated as "×". When less than 3% by mass of the polymer remains on the sieve, the result is evaluated as "○".

[0389] (4) Evaluation methods of odor and color

[0390] In the present invention, the odor is evaluated by the following method. First, 100 g of a propylene-based polymer is placed in a clean glass bottle; the bottle is capped, and the capped glass bottle is heated in an oven at 100° C. for 4 hours; and immediately after the glass bottle is taken out of the oven, the bottle is opened to evaluate the presence or absence of an odor derived from alcohol or sulfur, etc. When such an odor is present, the result is evaluated as “×”. When such an odor is not present, the result is evaluated as “○”.

[0391] The color evaluation was performed as follows. The same sample was used and heated in an oven at 100° C. for 4 hours. Immediately after the sample was taken out of the oven, a visual evaluation was performed to determine whether yellowing or the like occurred in the sample. When a color change was found, the result was evaluated as “×”. When there was no color change, the result was evaluated as “○”.

[0392] (5) Measurement of flexural modulus

[0393] The test piece was molded by using an EC100 injection molding machine manufactured by Shibaura Machine Co., Ltd. The test piece was conditioned in a constant temperature chamber controlled at room temperature of 23°C ± 1°C and relative humidity of 50% ± 5% for 7 days. Using the test piece, the flexural modulus was obtained in accordance with JIS K7171.

[0394] (6) Evaluation criteria for environmental adaptability

[0395] In the production of propylene-based polymers, when a reaction inhibitor derived from a biomass raw material containing impurities within a specific concentration is used as a substitute for a reaction inhibitor derived from fossil resources, the environmental adaptability is evaluated as "○". When a reaction inhibitor derived from fossil resources is used, the environmental adaptability is evaluated as "×". When the production of propylene-based polymers does not meet either of them, the environmental adaptability is evaluated as "-".

[0396] (7) Analysis of impurity levels in reaction inhibitors

[0397] The water content was measured by using a Karl Fischer titrator in accordance with JIS K8101.

[0398] The methanol content was measured by gas chromatography using a hydrogen flame ionization detector in accordance with JAAS001 6.4.

[0399] After a treatment of adding 9 mL of 1.0 M nitric acid per 1 mL of a reaction inhibitor, the content of copper atoms was measured by using ICP-AES in accordance with JIS K010151.2.

[0400] After the reaction inhibitor was burned and decomposed in an argon / oxygen atmosphere, the content of sulfur atoms was measured by an ultraviolet fluorescence method in accordance with JIS K2541-6.

[0401] (8) Identification of reaction inhibitors derived from biomass

[0402] By using oxygen isotopes 18 The biobasedness measurement method of O confirms that the reaction inhibitor (ethanol) used is a reaction inhibitor derived from biomass.

[0403] Using a clean microsyringe, 0.2 μL of the measurement sample (ethanol) was directly injected into the decomposition furnace of the pyrolysis type element analyzer pretreatment system TC / EA (manufactured by THERMO ELECTRON Co., Ltd.). The injected sample was decomposed at a temperature of 1400° C. in the decomposition furnace. The decomposed gas thus generated was then introduced into an isotope ratio mass spectrometer (product name: DELTA PLUS XP, manufactured by Thermo Electoron Co., Ltd.) to measure 16O and 18 Oxygen isotope abundance ratio.

[0404] Next, the hydrogen isotope D and oxygen isotope D were measured. 18 Oxygen isotope abundance ratio of VPDB (Vienna PDB) of O standard material.

[0405] By substituting these oxygen isotope abundance ratio values ​​into the following formula, the oxygen isotope abundance ratio parameter δ of the measured sample (ethanol) is finally obtained: 18 O.

[0406] δ 18 O = (oxygen isotope abundance ratio of sample / oxygen isotope abundance ratio of standard material - 1) × 1000

[0407] Using Delta 18 O, the value of the oxygen isotope abundance ratio in the evaluation sample.

[0408] When δ is calculated by the above formula 18 When the value of O is greater than 0, the reaction inhibitor used is judged to be ethanol derived from biomass. 18 When the O value is equal to or less than 0, it is judged to be ethanol derived from petrochemical products.

[0409] [Catalyst production example]

[0410] (1) Preparation of solid catalyst components for olefin polymerization

[0411] The autoclave with a capacity of 10L equipped with a solid component preparation stirrer is fully replaced with nitrogen, and 2L of refined toluene is introduced into the autoclave. At room temperature, 200g Mg(OEt)2 and 1L TiCl4 are added. After the temperature of the autoclave is raised to 90°C, 40ml of di-n-butyl phthalate and 10ml of diethyl phthalate are introduced into the autoclave. Then, the temperature is raised to 110°C for reaction for 3 hours. The reaction product thus obtained is fully washed with refined toluene. Then, refined toluene is introduced so that the total amount of solution is controlled to 2L. At room temperature, 1L TiCl4 is added, and the temperature is raised to 110°C for reaction for 2 hours. The reaction product thus obtained is fully washed with refined toluene. Then, refined toluene is introduced so that the total amount of solution is controlled to 2L. At room temperature, 1L TiCl4 is added, and the temperature is raised to 110°C for reaction for 2 hours. The reaction product thus obtained is fully washed with refined toluene. In addition, using refined n-heptane, toluene is replaced with n-heptane to obtain the slurry of solid component. A portion of the slurry is sampled, dried and analyzed. As a result, the Ti content of the solid component is 1.7% by mass. Next, the autoclave with a capacity of 20L equipped with a stirrer is fully purged with nitrogen, and the amount of the solid component is 100g (0.036mol Ti) of the solid component slurry is imported into the autoclave. Refined n-heptane is imported into the autoclave to control the concentration of the solid component to 25g / L. Then, 50ml SiCl4 is added, and the reaction is carried out at 90°C for 1 hour. The reaction product thus obtained is fully washed with refined n-heptane, and the liquid level is controlled to 4L by importing refined n-heptane. Next, 25 ml of [CH2=CH-]2SiMe2, 18 ml of (i-Pr)2Si(OMe)2 and a dilution of triethylaluminum in n-heptane in an amount of 40 g (0.35 mol) of triethylaluminum were added thereto, and the reaction was carried out at 40° C. for 2 hours. The reaction product thus obtained was fully washed with refined n-heptane.

[0412] A portion of the slurry thus obtained was sampled, dried, and analyzed. As a result, 1.3 mass % of Ti and 7.7 mass % of (i-Pr) 2 Si(OMe) 2 were contained in the solid component.

[0413] (2) Preparation of prepolymerized catalyst for olefin polymerization

[0414] Using 100g (0.025mol Ti) of the solid component obtained above, prepolymerization is carried out by the following process. Refined n-heptane is introduced into the above-mentioned slurry to control the concentration of the solid component to 20g / L. After the slurry is cooled to 10°C, a dilution of triethylaluminum in n-heptane of 15g (0.132mol) of triethylaluminum is added thereto, and 280g of propylene is supplied over 4 hours. After the propylene supply is completed, the reaction is further continued for 30 minutes. Then, the gas phase portion thus formed is fully replaced with nitrogen, and the reaction product is fully washed with refined n-heptane. The slurry thus obtained is extracted from the autoclave and vacuum dried to obtain a solid catalyst component. As a result of analyzing the solid catalyst component, it is found that 1.9g of polypropylene is contained per 1 gram of solid component, and 0.88% by mass of Ti and 6.8% by mass of (i-Pr)2Si(OMe)2 are contained in the part obtained by removing polypropylene therefrom of the solid catalyst component.

[0415] (Example 1)

[0416] (First polymerization step)

[0417] A stainless steel autoclave (content volume 3.0 L) equipped with a stirrer and a temperature controller was heated and dried by vacuumization and then cooled to room temperature. Then, the interior of the autoclave was replaced with propylene gas, and 70.7 mg of triethylaluminum was introduced into the autoclave. Then, 9000 ml of hydrogen was introduced therein, and then 1000 g of liquefied propylene was introduced. After the internal temperature was adjusted to 60 ° C, a prepolymerization catalyst for olefin polymerization was pressed in by argon gas so that the solid catalyst component other than polypropylene was 5.0 mg, thereby initiating the polymerization of the first polypropylene-based polymer. After one hour, the unreacted liquefied monomer was purged to stop the polymerization. A portion of the polymer thus formed was analyzed by MFR. As a result, the polymer was a crystalline polypropylene polymer with a melt flow rate of 107 g / 10 min.

[0418] After sampling a portion of the polymer produced in the first step, 10 mg of bioethanol (biomass-derived ethanol purchased from FUJIFILM Wako Pure Chemical Corporation) was introduced into the reactor. Then, the bioethanol was brought into contact with the first propylene-based polymer produced in the first step by stirring them for 5 minutes using a stirrer. In this way, a biomass-derived reaction inhibitor was added between the first step and the second step.

[0419] The bioethanol used contained the following impurities: 1688 mass ppm of water, 428 mass ppm of methanol, 2.4 mass ppm of sulfur, and 54 mass ppb of copper.

[0420] (Second polymerization step)

[0421] Using an autoclave (internal volume 20 L) equipped with a stirrer and a temperature controller different from the polymerization reactor used in the first step, the gas to be used for polymerization in the second step was adjusted. The temperature was adjusted to 95° C. The composition of the mixed gas was as follows: 0.54 mol% of hydrogen, 62.7 mol% of propylene, 36.3 mol% of ethylene, and 0.50 mol% of nitrogen.

[0422] After the contact with the reaction inhibitor was completed, the temperature of the 3.0 L autoclave was raised to 70° C., and the mixed gas was supplied thereto until the total pressure of the reactor became 1.0 MPaG, thereby initiating the polymerization of step 2. While the polymerization temperature was maintained at 70° C. and the reaction pressure was maintained at 1.0 MPaG, the polymerization reaction was carried out for 1 hour; further, the polymerization reaction was stopped by purging the unreacted residual monomers, thereby obtaining propylene-based polymer-1.

[0423] The obtained polymer was dried under reduced pressure at 90°C for 1 hour. Then, various analyses of the dried polymer were performed, and the following results were obtained: MFR = 7.7 g / 10 min; the ratio (Wc) of the propylene copolymer portion produced in the second step was 32.2% by mass; the ethylene content (Gv) in the propylene-ethylene copolymer was 41% by mass; and the intrinsic viscosity (η) of the propylene-ethylene copolymer was 4.0 dL / g. As a result of the sensory test, the evaluation result of the odor was good, and the result of the visual evaluation of the powder color was "good appearance". The measured value of the flexural modulus was 860 MPa.

[0424] (Example 2)

[0425] Propylene-based polymer-2 was obtained by changing the production method of Example 1 as follows.

[0426] The amount of the reaction inhibitor supplied between the first step and the second step was changed to 20 mg.

[0427] The composition of the mixed gas used in the second step was changed to the following composition: 54.5 mol% of propylene, 36.3 mol% of ethylene, 0.54 mol% of hydrogen and 8.7 mol% of nitrogen.

[0428] Propylene-based polymer-2 was produced in the same manner as in Example 1 except for the above changes.

[0429] As a result of analyzing the obtained propylene polymer-2, the following results were obtained: MFR=13g / 10min; the ratio (Wc) of the propylene copolymer part produced in the second step was 25.5% by mass; the ethylene content (Gv) in the propylene-ethylene copolymer was 41% by mass; and the intrinsic viscosity (η) of the propylene-ethylene copolymer was 4.0dL / g. As a result of the sensory test, the evaluation result of the odor was good, and the result of the visual evaluation of the powder color was also "good appearance". The measured value of the flexural modulus was 1000MPa.

[0430] (Example 3)

[0431] Propylene-based polymer-3 was obtained by changing the production method of Example 1 as follows.

[0432] The amount of the reaction inhibitor supplied between the first step and the second step was changed to 40 mg.

[0433] The composition of the mixed gas used in the second step was changed to the following composition: 56.0 mol % of propylene, 34.0 mol % of ethylene, 0.60 mol % of hydrogen and 9.4 mol % of nitrogen.

[0434] Propylene-based polymer-3 was produced in the same manner as in Example 1 except for the above changes.

[0435] As a result of analyzing the obtained propylene polymer-3, the following results were obtained: MFR=88g / 10min; the ratio (Wc) of the propylene copolymer part produced in the second step was 3.0% by mass; the ethylene content (Gv) in the propylene-ethylene copolymer was 40% by mass; and the intrinsic viscosity (η) of the propylene-ethylene copolymer was 3.5dL / g. As a result of the sensory test, the evaluation result of the odor was good, and the result of the visual evaluation of the powder color was also "good appearance". The measured value of the flexural modulus was 1900MPa.

[0436] (Example 4)

[0437] Propylene-based polymer-4 was obtained by changing the production method of Example 1 as follows.

[0438] The amount of the reaction inhibitor supplied between the first step and the second step was changed to 20 mg.

[0439] The composition of the mixed gas used in the second step was changed to the following composition: 54.5 mol% of propylene, 36.3 mol% of ethylene, 0.54 mol% of hydrogen, and 8.7 mol% of nitrogen. In addition, dimethyl sulfide (purchased from FUJIFILM WakoPure Chemical Corporation) was used to adjust the concentration to 8.4×10 -5mg / mL ultra-dehydrated hexane solution and added at the same feeding timing as the reaction inhibitor.

[0440] Propylene-based polymer-4 was produced in the same manner as in Example 1 except for the above changes.

[0441] As a result of analyzing the obtained propylene polymer-4, the following results were obtained: MFR=14g / 10min; the ratio (Wc) of the propylene copolymer part produced in the second step was 24.5% by mass; the ethylene content (Gv) in the propylene-ethylene copolymer was 43% by mass; and the intrinsic viscosity (η) of the propylene-ethylene copolymer was 4.0dL / g. As a result of the sensory test, the evaluation result of the odor was good, and the result of the visual evaluation of the powder color was also "good appearance". The measured value of the flexural modulus was 950MPa.

[0442] (Example 5)

[0443] Propylene-based polymer-5 was obtained by changing the production method of Example 1 as follows.

[0444] The amount of the reaction inhibitor supplied between the first step and the second step was changed to 20 mg.

[0445] The composition of the mixed gas used in the second step was changed to the following composition: 54.5 mol% of propylene, 36.3 mol% of ethylene, 0.54 mol% of hydrogen, and 8.7 mol% of nitrogen. In addition, copper acetate (purchased from FUJIFILM Wako Pure Chemical Corporation) was used to adjust the concentration to 1.0×10 -7 mg / mL ultra-dehydrated hexane solution and added at the same feeding timing as the reaction inhibitor.

[0446] Propylene-based polymer-5 was produced in the same manner as in Example 1 except for the above changes.

[0447] As a result of analyzing the obtained propylene polymer-2, the following results were obtained: MFR=14g / 10min; the ratio (Wc) of the propylene copolymer part produced in the second step was 24.9% by mass; the ethylene content (Gv) in the propylene-ethylene copolymer was 42% by mass; and the intrinsic viscosity (η) of the propylene-ethylene copolymer was 4.0dL / g. As a result of the sensory test, the evaluation result of the odor was good, and the result of the visual evaluation of the powder color was also "good appearance". The measured value of the flexural modulus was 930MPa.

[0448] (Comparative Example 1)

[0449] Propylene-based polymer-C1 was obtained by changing the production method of Example 1 as follows.

[0450] The reaction inhibitor supplied between the first step and the second step was changed to ethanol derived from petrochemical products (ultra-dehydrated grade, purchased from FUJIFILM Wako Pure Chemical Corporation). The ethanol derived from petrochemical products contained the following impurities: 10 mass ppm or less of water and 20 mass ppm or less of methanol. No sulfur atoms and copper atoms were detected therefrom.

[0451] Propylene-based polymer-C1 was produced in the same manner as in Example 1 except for the above changes.

[0452] As a result of analyzing the obtained propylene polymer-C1, the following results were obtained: MFR=9.2g / 10min; the ratio (Wc) of the propylene copolymer part produced in the second step was 30% by mass; the ethylene content (Gv) in the propylene-ethylene copolymer was 40% by mass; and the intrinsic viscosity (η) of the propylene-ethylene copolymer was 4.0dL / g. As a result of the sensory test, the evaluation result of the odor was good, and the result of the visual evaluation of the powder color was also "good appearance". The measured value of the flexural modulus was 850MPa.

[0453] (Comparative Example 2)

[0454] Propylene-based polymer-C2 was obtained by changing the production method of Comparative Example 1 as follows.

[0455] The amount of the reaction inhibitor supplied between the first step and the second step was changed to 20 mg.

[0456] Propylene-based polymer-C2 was produced in the same manner as in Example 1 except for the above changes.

[0457] As a result of analyzing the obtained propylene polymer-C2, the following results were obtained: MFR=21g / 10min; the ratio (Wc) of the propylene copolymer part produced in the second step was 20% by mass; the ethylene content (Gv) in the propylene-ethylene copolymer was 40% by mass; and the intrinsic viscosity (η) of the propylene-ethylene copolymer was 4.0dL / g. As a result of the sensory test, the evaluation result of the odor was good, and the result of the visual evaluation of the powder color was also "good appearance". The measured value of the flexural modulus was 1220MPa.

[0458] (Comparative Example 3)

[0459] Propylene-based polymer-C3 was obtained by changing the production method of Comparative Example 1 as follows.

[0460] The amount of the reaction inhibitor supplied between the first step and the second step was changed to 40 mg.

[0461] Propylene-based polymer-C3 was produced in the same manner as in Example 1 except for the above changes.

[0462] As a result of analyzing the obtained propylene polymer-C3, the following results were obtained: MFR=91g / 10min; the ratio (Wc) of the propylene copolymer part produced in the second step was 2.0% by mass; the ethylene content (Gv) in the propylene-ethylene copolymer was 40% by mass; and the intrinsic viscosity (η) of the propylene-ethylene copolymer was 4.0dL / g. As a result of the sensory test, the evaluation result of the odor was good, and the result of the visual evaluation of the powder color was also "good appearance". The measured value of the flexural modulus was 1900MPa.

[0463] (Comparative Example 4)

[0464] Propylene-based polymer-C4 was obtained by changing the production method of Comparative Example 1 as follows.

[0465] No reaction inhibitors were used.

[0466] Propylene-based polymer-C4 was produced in the same manner as in Example 1 except for the above changes.

[0467] As a result of analyzing the obtained propylene polymer-C4, the following results were obtained: MFR=2.1g / 10min; the ratio (Wc) of the propylene copolymer part produced in the second step was 48% by mass; the ethylene content (Gv) in the propylene-ethylene copolymer was 40% by mass; and the intrinsic viscosity (η) of the propylene-ethylene copolymer was 4.0dL / g. As a result of the sensory test, the evaluation result of the odor was good, and the result of the visual evaluation of the powder color was also "good appearance". As a result of passing the propylene polymer-C4 through a sieve with an opening size of 3350μm, it was found that 5% by mass of aggregated block polymers were formed. The measured value of the flexural modulus was 510MPa.

[0468] (Comparative Example 5)

[0469] Propylene-based polymer-C5 was obtained by changing the production method of Comparative Example 1 as follows.

[0470] The amount of the reaction inhibitor supplied between the first step and the second step was changed to 20 mg.

[0471] Propylene-based polymer-C5 was produced in the same manner as in Example 1 except for the above changes.

[0472] As a result of analyzing the obtained propylene polymer-C5, the following results were obtained: MFR=14g / 10min; the ratio (Wc) of the propylene copolymer part produced in the second step was 24.9% by mass; the ethylene content (Gv) in the propylene-ethylene copolymer was 42% by mass; and the intrinsic viscosity (η) of the propylene-ethylene copolymer was 4.0dL / g. As a result of the sensory test, the evaluation result of the odor was poor, and the result of the visual evaluation of the powder color was also "poor appearance". The measured value of the flexural modulus was 950MPa.

[0473] (Comparative Example 6)

[0474] Propylene-based polymer-C6 was obtained by changing the production method of Comparative Example 1 as follows.

[0475] The amount of the reaction inhibitor supplied between the first step and the second step was changed to 20 mg.

[0476] Propylene-based polymer-C6 was produced in the same manner as in Example 1 except for the above changes.

[0477] As a result of analyzing the obtained propylene polymer-C6, the following results were obtained: MFR=9.2g / 10min; the ratio (Wc) of the propylene copolymer part produced in the second step was 30% by mass; the ethylene content (Gv) in the propylene-ethylene copolymer was 40% by mass; and the intrinsic viscosity (η) of the propylene-ethylene copolymer was 4.0dL / g. As a result of the sensory test, the evaluation result of the odor was poor, and the result of the visual evaluation of the powder color was "good appearance". The measured value of the flexural modulus was 710MPa.

[0478] The polymerization results and the evaluation results are shown in Tables 1 and 2.

[0479] [Table 1]

[0480] Table 1

[0481]

[0482] [Table 2]

[0483] Table 2

[0484]

[0485] As a result of comparing Examples 1, 2 and 3 with Comparative Examples 1, 2 and 3, respectively, it was revealed that, compared with Comparative Example 4 in which no reaction inhibitor was used, Examples 1 to 3 could provide production comparable to that of Comparative Examples 1 to 3 each using a reaction inhibitor derived from a fossil fuel despite using a reaction inhibitor containing a certain amount of impurities derived from biomass.

[0486] From the results of Examples 1 to 5 and Comparative Examples 1 to 6, it was revealed that even when bioethanol containing a certain amount of impurities was used as a reaction inhibitor, the bioethanol could be used without causing a significant decrease in productivity and long-term operational instability due to the formation of block resin, and the bioethanol was good for the environment because it was ethanol derived from biomass. In addition, it was revealed that when the moisture content of the reaction inhibitor exceeded a predetermined amount, production problems (such as equipment failure caused by moisture accumulated in the production equipment) may occur; however, when the moisture content was lower than the predetermined amount, the reaction inhibitor could be used without any production problems.

Claims

1. A method for producing a propylene polymer, in, In the first step, a propylene homopolymer or a copolymer of propylene and at least one monomer selected from the group consisting of α-olefins having 2 to 10 carbon atoms other than propylene is produced as a first propylene-based polymer using one or more polymerization reactors in the presence of an olefin polymerization catalyst; wherein, in the subsequent second step, a propylene homopolymer or a copolymer of propylene and at least one monomer selected from the group consisting of α-olefins having 2 to 10 carbon atoms other than propylene is produced as the second propylene-based polymer using one or more polymerization reactors and in the presence of the first propylene-based polymer; and At least one selected from the group consisting of the first step, the second step, and a step between the first step and the second step includes adding a biomass-derived reaction inhibitor containing 5 to 2000 ppm by mass of water. 2 . The method for producing a propylene-based polymer according to claim 1 , wherein the reaction inhibitor further contains 0.1 to 1000 ppm by mass of methanol. 3 . 3 . The method for producing a propylene-based polymer according to claim 1 , wherein the reaction inhibitor further contains 0.1 to 5 ppm by mass of sulfur atoms and 0.1 to 100 ppb by mass of copper atoms. 4 . The method for producing a propylene-based polymer according to claim 1 , wherein the reaction inhibitor is ethanol derived from biomass.

5. The method for producing a propylene-based polymer according to any one of claims 1 to 4, wherein the olefin polymerization catalyst comprises a solid catalyst component (A) comprising the following (A1), (A2) and (A3) and optionally comprising the following (A4) and the following component (B): (A1) A solid component comprising magnesium, titanium, a halogen and an electron-donating compound serving as an internal donor (A2) Organic aluminum compounds (A3) Organic silicon compounds other than vinylsilane compounds (A4) Vinylsilane compound (B) Organic aluminum compounds.

6. The method for producing a propylene-based polymer according to any one of claims 1 to 5, wherein the second propylene-based polymer produced in the second step is a copolymer of propylene and at least one monomer selected from the group consisting of α-olefins having 2 to 10 carbon atoms other than propylene, and the content of the at least one monomer selected from the group consisting of α-olefins having 2 to 10 carbon atoms other than propylene is in the range of 20 mass % to 80 mass %.

7. The method for producing a propylene-based polymer according to claim 5 or 6, wherein the amount of the reaction inhibitor added is 0.01 g to 30 g relative to 1 g of the total amount of the solid catalyst component (A).

Citation Information

Patent Citations

  • POLYMERIZATION CATALYST FOR alpha-OLEFIN AND PROCESS FOR PRODUCTION OF alpha-OLEFIN POLYMER THEREWITH

    JP2004124090A

  • alpha-OLEFIN POLYMERIZATION CATALYST AND METHOD FOR PRODUCING alpha-OLEFIN POLYMER USING THE SAME

    JP2006225449A